Adhesive composition, adhesive, adhesive sheet, and polyester resin for tackifier
A polyester resin-based adhesive composition with blocked reactive terminals addresses the issues of chemical resistance and tackiness in pressure-sensitive adhesives, providing enhanced performance for electronic components.
Patent Information
- Application Number
- JP2021012291
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-31
- Filing Date
- 2021-01-28
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2041-01-28
AI Technical Summary
Existing pressure-sensitive adhesive compositions using acrylic and polyester resins face issues with resistance to highly polar chemicals like alcohol, poor tackiness, and reduced adhesive strength over time due to crosslinking and poor compatibility of tackifiers.
A pressure-sensitive adhesive composition containing a polyester resin with structural units derived from polyvalent carboxylic acid and polyol, where reactive molecule terminals are blocked with a blocking agent, enhancing adhesive strength, chemical resistance, and tackiness.
The composition achieves excellent adhesive strength, chemical resistance, and tackiness, particularly suitable for electronic components, while maintaining stability and compatibility with other polymers.
Smart Images

Figure 0007615709000001 
Figure 0007615709000002 
Figure 0007615709000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a pressure-sensitive adhesive composition, a pressure-sensitive adhesive, a pressure-sensitive adhesive sheet, and a polyester-based resin for tackifier, and more specifically to a pressure-sensitive adhesive composition, a pressure-sensitive adhesive, and a pressure-sensitive adhesive sheet that are excellent in adhesive strength, chemical resistance, holding power, and tackiness, and also to a novel polyester-based resin for tackifier. [Background technology]
[0002] It has been known that polyester resins, when combined with a polycarboxylic acid component and a polyol component, can have excellent chemical resistance, plasticizer resistance, mechanical strength, etc., and this has also been studied in the field of pressure-sensitive adhesives (adhesives). In addition, in portable electronic devices (e.g., mobile phones, personal digital assistants, etc.) equipped with an image display device or an input device, adhesive tapes are used for assembly. Specifically, double-sided adhesive tapes are used to adhere a cover panel for protecting the surface of a portable electronic device to a touch panel module or a display panel module, or to adhere a touch panel module to a display panel module. Such double-sided adhesive tapes are punched into a shape such as a picture frame, and are used by being placed around a display screen. Double-sided adhesive tapes are also used for fixing vehicle parts to a vehicle body, and adhesives using acrylic resins are being considered for such adhesives.
[0003] In this situation, in recent years, due to the miniaturization, weight reduction, and cost reduction of electronic devices, electronic devices that are always worn or kept at hand, such as mobile phones, smartphones, and wearable terminals, have become widespread. Since such portable electronic devices are operated with bare hands using touch panels, etc., they are exposed to chemicals such as sebum and alcohol such as perfume, insect repellent spray, hand washing detergent, and disinfectant sheets, and therefore high adhesive strength and chemical resistance to sebum, alcohol, etc. are required. For example, Patent Document 1 proposes an acrylic pressure-sensitive adhesive composition containing an acrylic resin and a tackifier resin having a predetermined hydroxyl value. Patent Document 2 proposes a polyester-based pressure-sensitive adhesive composition containing a polyester resin and a tackifier. Furthermore, Patent Document 3 proposes an acrylic pressure-sensitive adhesive composition containing an acrylic resin, a reactive compound, and a ring-structure-containing polyester having a predetermined acid value. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2020-7477 A [Patent Document 2] JP 2014-169419 A [Patent Document 3] JP 2019-6925 A Summary of the Invention [Problem to be solved by the invention]
[0005] In the technology disclosed in the above Patent Document 1, a tackifier resin with a high hydroxyl value is blended with an acrylic resin, but since the base polymer is an acrylic resin, there remains a problem with resistance to highly polar chemicals such as alcohol.
[0006] In addition, in the technology disclosed in Patent Document 2, a tackifier with a high softening point, such as a rosin ester or terpene resin, is blended with a polyester resin. Generally, a tackifier with a high softening point is often blended to impart cohesive strength at high temperatures, but such a tackifier has problems such as reduced tackiness at room temperature, poor appearance due to low compatibility, and poor resistance to highly polar chemicals such as alcohol.
[0007] In addition, in the technology disclosed in Patent Document 3, a polyester resin is blended with an acrylic resin. However, since such a polyester resin has a functional group, there remain problems such as storage stability as a pressure-sensitive adhesive composition, a decrease in tackiness as a pressure-sensitive adhesive due to the progress of a reaction with a crosslinking agent, and poor resistance to highly polar chemicals such as alcohol.
[0008] Under these circumstances, an object of the present invention is to provide a pressure-sensitive adhesive composition having excellent adhesive strength, chemical resistance, holding power and tackiness, and further to provide a pressure-sensitive adhesive, a pressure-sensitive adhesive sheet, and a polyester-based resin for a tackifier. [Means for solving the problem]
[0009] However, the present inventors have conducted extensive research in light of these circumstances and have found that, in a pressure-sensitive adhesive composition containing a polymer (A) and a polyester-based resin (B), by using, as the polyester-based resin (B), a polyester-based resin (B) having a structural unit derived from a polyvalent carboxylic acid (b1) and a structural unit derived from a polyol (b2) and having at least one reactive molecular end blocked, a polyester-based pressure-sensitive adhesive composition excellent in adhesive strength, chemical resistance, holding power and tackiness can be obtained, thereby completing the present invention.
[0010] That is, the gist of the present invention is the following [1] to
[17] . [1] A pressure-sensitive adhesive composition comprising a polymer (A) and a polyester-based resin (B) having structural units derived from a polyvalent carboxylic acid (b1) and structural units derived from a polyol (b2), and in which at least one reactive molecular end is blocked. [2] The pressure-sensitive adhesive composition according to [1], wherein at least one reactive molecular end of the polyester resin (B) is blocked with a blocking agent (b3) having a number average molecular weight of 50 to 5,000. [3] The pressure-sensitive adhesive composition according to [1] or [2], wherein the polyester resin (B) has a glass transition temperature (TgB) of -80 to 30°C. [4] The pressure-sensitive adhesive composition according to any one of [1] to [3], wherein the polyester resin (B) has a number average molecular weight of 300 to 30,000. [5] The pressure-sensitive adhesive composition according to any one of [1] to [4], wherein the polyester resin (B) has a hydroxyl value of 10 mgKOH / g or less. [6] The pressure-sensitive adhesive composition according to any one of [1] to [5], wherein the polyester resin (B) has an acid value of 3 mgKOH / g or less. [7] The pressure-sensitive adhesive composition according to any one of [1] to [6], wherein the polyester resin (B) has a heat of crystalline fusion of 10 J / g or less. [8] The pressure-sensitive adhesive composition according to any one of [2] to [7], wherein at least one of the structural unit derived from the polyvalent carboxylic acid (b1), the structural unit derived from the polyol (b2), and the blocking agent (b3) contains an aromatic structural unit. [9] The pressure-sensitive adhesive composition according to any one of [1] to [8], wherein the content of the polyester resin (B) is 0.1 to 180 parts by weight based on 100 parts by weight of the polymer (A).
[10] The pressure-sensitive adhesive composition according to any one of [1] to [9], wherein the polymer (A) is a polyester resin having a structural unit derived from a polyvalent carboxylic acid (a1) and a structural unit derived from a polyol (a2).
[11] The pressure-sensitive adhesive composition according to
[10] , wherein the polyester resin is a polyester resin containing an aromatic structural unit in at least one of the structural units derived from the polyvalent carboxylic acid (a1) and the structural units derived from the polyol (a2).
[12] The pressure-sensitive adhesive composition according to any one of [1] to
[11] , wherein the polymer (A) has a glass transition temperature (TgA) of -70 to 40°C.
[13] The pressure-sensitive adhesive composition according to any one of [1] to
[12] , wherein the glass transition temperature (TgA) of the polymer (A) is higher than the glass transition temperature (TgB) of the polyester resin (B).
[14] A pressure-sensitive adhesive obtained by crosslinking the pressure-sensitive adhesive composition according to any one of [1] to
[13] .
[15] An adhesive sheet having an adhesive layer containing the adhesive according to
[14] .
[16] The adhesive sheet according to
[15] , which is used for bonding electronic components.
[17] A polyester-based resin for use as a tackifier, which has structural units derived from a polyvalent carboxylic acid (b1) and structural units derived from a polyol (b2), and at least one reactive molecular end is blocked with a blocking agent (b3), and at least one of the structural units derived from the polyvalent carboxylic acid (b1), the structural units derived from the polyol (b2), and the blocking agent (b3) has an aromatic structural unit.
[0011] In general, a tackifier is blended in a pressure-sensitive adhesive to improve the adhesive strength to the adherend, and in this case, it is considered to introduce a polar group into the resin structure of the tackifier in order to improve compatibility with the base agent and adhesion to the adherend. Therefore, for example, when blending a polyester resin as a tackifier, it is commonly believed that it is better to blend the polyester resin in a state in which it has a hydroxyl group or a carboxyl group. However, in the present invention, a polyester resin in which the hydroxyl or carboxyl groups in the polyester resin are blocked is deliberately blended, and as a result, the adhesive strength is unexpectedly not reduced, and the chemical resistance, holding power and tackiness are excellent, thereby achieving the object of the present invention. Effect of the Invention
[0012] The pressure-sensitive adhesive composition of the present invention contains a polymer (A) and a polyester resin (B) having a structural unit derived from a polyvalent carboxylic acid (b1) and a structural unit derived from a polyol (b2), and having at least one reactive molecular end blocked. Therefore, it has excellent adhesive strength, chemical resistance, holding power, and tackiness, and is particularly useful as a pressure-sensitive adhesive for electronic and optical components.
[0013] Furthermore, the polyester resin for tackifier of the present invention has a structural unit derived from a polyvalent carboxylic acid (b1) and a structural unit derived from a polyol (b2), at least one reactive molecular end is blocked with a blocking agent (b3), and at least one of the structural unit derived from the polyvalent carboxylic acid (b1), the structural unit derived from the polyol (b2), and the blocking agent (b3) has an aromatic structural unit, and therefore has excellent tackifying performance and is useful as a tackifier for polymers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The configuration of the present invention will be described in detail below, but these are merely examples of preferred embodiments. In the present invention, "y and / or z (y and z are optional structures or components)" means three combinations: y only, z only, and y and z.
[0015] The pressure-sensitive adhesive composition of the present invention contains a polymer (A) and a polyester-based resin (B) having a structural unit derived from a polyvalent carboxylic acid (b1) and a structural unit derived from a polyol (b2), and in which at least one reactive molecular end is blocked. Each of the components used in the pressure-sensitive adhesive composition of the present invention will be described in detail below.
[0016] <Polymer (A)> The polymer (A) is the main component of the adhesive composition, and examples thereof include polyester resins, acrylic resins, urethane resins, and rubber resins. These may be used alone or in combination of two or more. Among them, polyester resins and acrylic resins are preferred in terms of adhesive strength and heat resistance, and polyester resins are particularly preferred in terms of chemical resistance and plasticizer resistance. The main component refers to a component that has a significant effect on the properties of the adhesive composition, and the content of the component is usually 30% by weight or more, preferably 50% by weight or more, of the entire adhesive composition. The polyester resin and the acrylic resin, which are preferred embodiments of the polymer (A), will be described below.
[0017] [Polyester Resin] The polyester-based resin that can be used in the present invention is one other than the polyester-based resin (B) described below, and is usually obtained by copolymerizing copolymerization components containing polyvalent carboxylic acids (a1) and polyol (a2) as constituent raw materials, and the polyester-based resin has, as its resin composition, structural units derived from the polyvalent carboxylic acids (a1) and structural units derived from the polyol (a2). From the viewpoint of excellent chemical resistance, it is preferable that the polyester-based resin contains an aromatic structural unit in at least one of the structural units derived from the polyvalent carboxylic acids (a1) and the structural units derived from the polyol (a2), and it is particularly preferable that the structural unit derived from the polyvalent carboxylic acids (a1) contains an aromatic structural unit. In the present invention, the term "carboxylic acids" includes not only carboxylic acids but also carboxylic acid derivatives such as carboxylic acid salts, carboxylic acid anhydrides, carboxylic acid halides, and carboxylic acid esters.
[0018] [Structural units derived from polycarboxylic acids (a1)] Examples of the structural unit derived from the polyvalent carboxylic acid (a1) include a structural unit derived from a divalent carboxylic acid and a structural unit derived from a trivalent or higher polyvalent carboxylic acid. It is preferable that the structural unit derived from a divalent carboxylic acid is contained in order to stably obtain a polyester resin.
[0019] Examples of the structural units derived from divalent carboxylic acids include structural units derived from aliphatic dicarboxylic acids such as malonic acids, dimethylmalonic acids, succinic acids, glutaric acids, adipic acids, trimethyladipic acids, pimelic acids, 2,2-dimethylglutaric acids, azelaic acids, sebacic acids, fumaric acids, maleic acids, itaconic acids, thiodipropionic acids, diglycolic acids, and 1,9-nonanedicarboxylic acids; Structural units derived from aromatic dicarboxylic acids such as phthalic acids, terephthalic acids, isophthalic acids, benzylmalonic acids, diphenic acids, 4,4'-oxydibenzoic acids, and also naphthalenedicarboxylic acids such as 1,8-naphthalenedicarboxylic acids, 2,3-naphthalenedicarboxylic acids, and 2,7-naphthalenedicarboxylic acids; Structural units derived from alicyclic dicarboxylic acids such as 1,3-cyclopentanedicarboxylic acids, 1,2-cyclohexanedicarboxylic acids, 1,3-cyclopentanedicarboxylic acids, 1,4-cyclohexanedicarboxylic acids, 2,5-norbornanedicarboxylic acids, and adamantanedicarboxylic acids; Structural units derived from dimer acids (mainly those having 36 to 44 carbon atoms) derived from oleic acid, linoleic acid, linolenic acid, erucic acid, etc.; and the like. Examples of the structural unit derived from trivalent or higher polyvalent carboxylic acids include structural units derived from trimellitic acids, pyromellitic acids, adamantanetricarboxylic acids, trimesic acids, and the like. These structural units derived from polyvalent carboxylic acids (a1) may be contained alone or in combination of two or more kinds.
[0020] Among the structural units derived from the polyvalent carboxylic acids (a1), it is preferable to include structural units derived from aromatic polyvalent carboxylic acids, particularly structural units derived from asymmetric aromatic dicarboxylic acids (a1-1), from the viewpoint of reducing the crystallinity of the polyester resin and excellent chemical resistance, and examples of structural units derived from asymmetric aromatic dicarboxylic acids (a1-1) include structural units derived from phthalic acids, isophthalic acids, 1,8-naphthalenedicarboxylic acids, 2,3-naphthalenedicarboxylic acids, 2,7-naphthalenedicarboxylic acids, etc. Among them, it is particularly preferable to include structural units derived from isophthalic acids from the viewpoint of reactivity.
[0021] The content of the structural unit derived from such aromatic polycarboxylic acids, particularly the structural unit derived from asymmetric aromatic dicarboxylic acids (a1-1), is preferably 5 to 100 mol%, more preferably 10 to 95 mol%, further preferably 20 to 90 mol%, particularly preferably 40 to 85 mol%, and particularly preferably 60 to 80 mol%, based on the total structural units derived from polycarboxylic acids (a1). If the content is too low, the chemical resistance tends to decrease, or the polyester resin tends to crystallize, making it difficult to obtain sufficient adhesive performance. If the content is too high, the initial adhesive strength (tack) tends to decrease.
[0022] In the present invention, from the viewpoint of improving the initial adhesive strength (tack), the structural unit derived from the polyvalent carboxylic acid (a1) preferably contains a structural unit derived from an aliphatic dicarboxylic acid (a1-2) having 4 or more carbon atoms (including the carbon of the carboxy group), more preferably contains an aliphatic dicarboxylic acid having 6 to 12 carbon atoms (including the carbon of the carboxy group), and particularly preferably contains a structural unit derived from an adipic acid, a sebacic acid, or an azelaic acid.
[0023] The content of the structural units derived from the aliphatic dicarboxylic acids (a1-2) having 4 or more carbon atoms is preferably 5 to 90 mol %, more preferably 10 to 80 mol %, further preferably 15 to 60 mol %, and particularly preferably 20 to 40 mol %, based on the total structural units derived from the polyvalent carboxylic acids (a1). If the content is too low, the glass transition temperature of the polyester resin becomes too high, and sufficient adhesive strength tends to be unavailable, whereas if the content is too high, chemical resistance tends to decrease, or the polyester resin tends to crystallize, and sufficient adhesive performance tends to be unavailable.
[0024] In the present invention, from the viewpoint of adhesive properties, it is also preferable that the structural units derived from the polyvalent carboxylic acids (a1) include structural units derived from asymmetric aromatic dicarboxylic acids (a1-1) and structural units derived from aliphatic dicarboxylic acids (a1-2) having 4 or more carbon atoms. In this case, the content ratio (molar ratio) of the structural units derived from the asymmetric aromatic dicarboxylic acids (a1-1) and the structural units derived from the aliphatic dicarboxylic acids (a1-2) having 4 or more carbon atoms is preferably (a1-1) / (a1-2)=1 / 99 to 99 / 1, more preferably 40 / 60 to 90 / 10, and particularly preferably 55 / 45 to 80 / 20.
[0025] In the present invention, the polyester resin may contain structural units derived from trivalent or higher polyvalent carboxylic acids (a1-3) for the purpose of increasing the number of branching points. Among these, it is preferable that the polyester resin contains structural units derived from trimellitic acids, since gelation is relatively unlikely to occur during production.
[0026] The content of the structural units derived from the trivalent or higher polyvalent carboxylic acids (a1-3) is preferably 10 mol % or less, particularly preferably 0.1 to 5 mol %, based on the total structural units derived from the polyvalent carboxylic acids (a1), in order to enhance the cohesive strength when used as an adhesive. If the content is too high, gelation tends to occur easily during the production of the polyester resin.
[0027] [Structural unit derived from polyol (a2)] Examples of the structural unit derived from the polyol (a2) include a structural unit derived from a dihydric alcohol and a structural unit derived from a trihydric or higher polyol.
[0028] Examples of the structural units derived from dihydric alcohols include structural units derived from aliphatic diols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, 1,3-propanediol, 2,4-dimethyl-2-ethylhexane-1,3-diol, 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 2-ethyl-2-butyl-1,3-propanediol, 2-ethyl-2-isobutyl-1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, and 2,2,4-trimethyl-1,6-hexanediol; Structural units derived from alicyclic diols such as 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, spiroglycol, tricyclodecane dimethanol, adamantanediol, and 2,2,4,4-tetramethyl-1,3-cyclobutanediol; Examples of structural units include those derived from aromatic diols such as 4,4'-thiodiphenol, 4,4'-methylenediphenol, 4,4'-dihydroxybiphenyl, o-, m-, and p-dihydroxybenzene, 2,5-naphthalenediol, p-xylenediol, and ethylene oxide adducts and propylene oxide adducts thereof. Further examples include structural units derived from fatty acid esters derived from castor oil, structural units derived from dimer diols derived from oleic acid, linoleic acid, linolenic acid, erucic acid, etc., and structural units derived from glycerol monostearate. Examples of the structural units derived from the trivalent or higher polyols include structural units derived from pentaerythritol, dipentaerythritol, tripentaerythritol, glycerin, trimethylolpropane, trimethylolethane, 1,2,4-butanetriol, 1,2,5-pentanetriol, 1,2,6-hexanetriol, 1,3,6-hexanetriol, and adamantanetriol. These structural units derived from polyol (a2) may be contained alone or in combination of two or more kinds.
[0029] In the present invention, from the viewpoint of lowering the glass transition temperature (Tg) of the polyester resin and improving the initial adhesive strength, it is preferable that the structural unit derived from the polyol (a2) contains a structural unit derived from an aliphatic diol (a2-1) having a linear structure, more preferably contains a structural unit derived from an aliphatic diol having 2 to 18 carbon atoms, and particularly preferably contains a structural unit derived from ethylene glycol, 1,4-butanediol, or 1,6-hexanediol.
[0030] The content of the structural units derived from the linear aliphatic diol (a2-1) is preferably 5 to 100 mol %, more preferably 10 to 95 mol %, further preferably 15 to 90 mol %, particularly preferably 20 to 80 mol %, and particularly preferably 30 to 70 mol %, based on the total structural units derived from the polyol (a2). If the content is too low, it tends to be difficult to obtain a stable resin formation.
[0031] Among the structural units derived from the polyol (a2), it is preferable to contain a structural unit derived from a diol (a2-2) having a hydrocarbon group on the side chain, because it can break the crystallinity. Examples of the structural unit derived from the diol (a2-2) having a hydrocarbon group on the side chain include dipropylene glycol, 2,4-dimethyl-2-ethylhexane-1,3-diol, 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 2-methyl-2-ethyl-1,3-propanediol, 2-ethyl-2-butyl-1,3-propanediol, 2-ethyl-2-isobutyl-1,3-propanediol, 1,3-butanediol, 3-methyl-1,5-pentanediol, ... Examples of the structural units include structural units derived from aliphatic diols having a branched structure, such as diols and 2,2,4-trimethyl-1,6-hexanediol, structural units derived from alicyclic diols having a branched structure, such as 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, spiroglycol, tricyclodecane dimethanol, adamantanediol, and 2,2,4,4-tetramethyl-1,3-cyclobutanediol, and structural units derived from dimer diols derived from oleic acid, erucic acid, etc. Among these, structural units derived from aliphatic diols having a branched structure are preferred, and structural units derived from 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), and 3-methyl-1,5-pentanediol are particularly preferred.
[0032] The content of the structural units derived from the diol (a2-2) having a hydrocarbon group in the side chain is preferably 5 to 95 mol %, more preferably 10 to 90 mol %, further preferably 15 to 80 mol %, particularly preferably 20 to 70 mol %, and particularly preferably 30 to 60 mol % based on the total structural units derived from the polyol (a2). If the content is too low, the resin tends to crystallize and it is difficult to obtain sufficient adhesive performance, while if the content is too high, the reaction time in the production of the polyester resin tends to be long.
[0033] Furthermore, in the present invention, it is also preferable that the structural unit derived from the polyol (a2) contains a structural unit derived from a trivalent or higher polyol (a2-3) in order to form a reactive site with the crosslinking agent (D) described later in the polyester resin and increase the cohesive force. Among the structural units derived from the trivalent or higher polyol (a2-3), structural units derived from trimethylolpropane, trimethylolethane, glycerin, pentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, and 1,2,6-hexanetriol are preferred, and the structural unit derived from trimethylolpropane is particularly preferred in terms of being relatively unlikely to generate gel.
[0034] The content of the structural units derived from the trihydric or higher polyol (a2-3) is preferably 10 mol % or less, more preferably 0.1 to 5 mol %, based on the total structural units derived from the polyol (a2). If the content of the structural units derived from the trihydric or higher polyol is too high, production of the polyester resin tends to be difficult.
[0035] Here, the proportion of structural units derived from each component of the polyester resin (compositional proportion) can be determined, for example, by NMR.
[0036] The polyester resin used in the present invention is produced by appropriately selecting the polyvalent carboxylic acids (a1) and the polyol (a2) within the above content ranges, and subjecting them to a polycondensation reaction in the presence of a catalyst by a known method.
[0037] The mixing ratio of the polyvalent carboxylic acids (a1) and the polyol (a2) is preferably 1 to 2 equivalents of the polyol (a2) per equivalent of the polyvalent carboxylic acids (a1), and particularly preferably 1.1 to 1.7 equivalents. If the mixing ratio of the polyol (a2) is too low, the acid value tends to be high, making it difficult to increase the molecular weight, and if it is too high, the yield tends to decrease.
[0038] In the polycondensation reaction, an esterification reaction is carried out first, and then the polycondensation reaction is carried out.
[0039] In such an esterification reaction, a catalyst is usually used, and specific examples thereof include titanium-based catalysts such as tetraisopropyl titanate and tetrabutyl titanate, antimony-based catalysts such as antimony trioxide, germanium-based catalysts such as germanium dioxide, and catalysts such as zinc acetate, manganese acetate, and dibutyltin oxide, and one or more of these are used. Among these, antimony trioxide, tetrabutyl titanate, germanium dioxide, and zinc acetate are preferred from the perspective of the balance between high catalytic activity and hue, and germanium dioxide is particularly preferred.
[0040] The amount of the catalyst is preferably 1 to 10,000 ppm by weight based on the total copolymerization components, particularly preferably 10 to 5,000 ppm, and further preferably 20 to 3,000 ppm. If the amount is too small, the polymerization reaction tends not to proceed sufficiently, while if the amount is too large, there is no advantage such as shortening the reaction time, and side reactions tend to occur easily.
[0041] The reaction temperature during the esterification reaction is preferably 200 to 300° C., particularly preferably 210 to 280° C., and further preferably 220 to 260° C. If the reaction temperature is too low, the reaction tends not to proceed sufficiently, and if the reaction temperature is too high, side reactions such as decomposition tend to occur easily. The pressure during the reaction is usually normal pressure.
[0042] After the esterification reaction, a polycondensation reaction is carried out. As reaction conditions for the polycondensation reaction, it is preferable to further compound the same amount of the catalyst as that used in the above esterification reaction, set the reaction temperature at preferably 220 to 280° C., particularly preferably 230 to 270° C., and gradually reduce the pressure of the reaction system to finally carry out the reaction at 5 hPa or less. If the reaction temperature is too low, the reaction tends not to proceed sufficiently, and if it is too high, side reactions such as decomposition tend to occur easily.
[0043] Thus, a polyester resin, which is one of the preferred embodiments of the polymer (A), is obtained.
[0044] [Acrylic resin] The acrylic resin that can be used in the present invention is obtained by copolymerizing a (meth)acrylic acid alkyl ester monomer (α1) with a functional group-containing monomer (α2), and, if necessary, with other copolymerizable monomers (α3). In addition, "(meth)acrylic" means acrylic or methacrylic, "(meth)acryloyl" means acryloyl or methacryloyl, and "(meth)acrylate" means acrylate or methacrylate, respectively.
[0045] The (meth)acrylic acid alkyl ester monomer (α1) has an alkyl group carbon number of usually 1 to 20, preferably 1 to 12, particularly preferably 1 to 8, and further preferably 1 to 4. If the carbon number is too large, the resulting acrylic resin and polyester resin (B) tend to be difficult to mix uniformly, resulting in a decrease in adhesive strength.
[0046] Examples of the (meth)acrylic acid alkyl ester monomer (α1) include aliphatic (meth)acrylic acid alkyl esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-propyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, and isostearyl (meth)acrylate; Examples of the alicyclic (meth)acrylic acid alkyl esters include cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, etc. These may be used alone or in combination of two or more kinds. Among the above (meth)acrylic acid alkyl ester monomers (α1), methyl (meth)acrylate, n-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate are preferred in terms of copolymerizability, adhesive properties, ease of handling, and ease of availability of raw materials.
[0047] The content of the (meth)acrylic acid alkyl ester monomer (α1) in the polymerization components is usually 30 to 99% by weight, preferably 40 to 98% by weight, and particularly preferably 50 to 95% by weight. When the content of the (meth)acrylic acid alkyl ester monomer (α1) is within the above range, the adhesive strength tends to be excellent.
[0048] Examples of the functional group-containing monomer (α2) include hydroxyl group-containing monomers, carboxyl group-containing monomers, amino group-containing monomers, amide group-containing monomers, glycidyl group-containing monomers, sulfonic acid group-containing monomers, acetoacetyl group-containing monomers, etc. These functional group-containing monomers can be used alone or in combination of two or more kinds.
[0049] The content of the functional group-containing monomer (α2) in the polymerization components is usually 0.01 to 30% by weight, preferably 0.2 to 20% by weight, and more preferably 0.5 to 10% by weight. If the content is too high, crosslinking will proceed before the drying step in making the adhesive sheet, and problems with coating properties will tend to occur, while if the content is too low, the degree of crosslinking will decrease, and sufficient adhesive strength will tend not to be obtained.
[0050] The hydroxyl group-containing monomer is preferably a hydroxyl group-containing (meth)acrylate monomer, and specific examples thereof include (meth)acrylic acid hydroxyalkyl esters such as 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 8-hydroxyoctyl (meth)acrylate; caprolactone-modified monomers such as caprolactone-modified 2-hydroxyethyl (meth)acrylate; oxyalkylene-modified monomers such as diethylene glycol (meth)acrylate and polyethylene glycol (meth)acrylate; and primary hydroxyl group-containing monomers such as 2-acryloyloxyethyl-2-hydroxyethyl phthalate; Secondary hydroxyl group-containing monomers such as 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 3-chloro-2-hydroxypropyl (meth)acrylate; Examples include tertiary hydroxyl group-containing monomers such as 2,2-dimethyl 2-hydroxyethyl (meth)acrylate. Among the above hydroxyl group-containing monomers, primary hydroxyl group-containing monomers are preferred because of their excellent reactivity with the crosslinking agent (D) described below, and 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are particularly preferred.
[0051] The content of the hydroxyl group-containing monomer in the polymerization components is usually 0.1 to 20% by weight, preferably 0.2 to 10% by weight, and more preferably 0.5 to 5% by weight. If the content is too high, crosslinking will proceed before the drying step in making the adhesive sheet, and problems with coating will tend to occur, whereas if the content is too low, the degree of crosslinking will decrease, and sufficient adhesive strength will tend not to be obtained.
[0052] Examples of the carboxy group-containing monomer include (meth)acrylic acid, (meth)acrylic acid dimer, crotonic acid, maleic acid, maleic anhydride, fumaric acid, citraconic acid, glutaconic acid, itaconic acid, acrylamido-N-glycolic acid, cinnamic acid, etc. Among these, (meth)acrylic acid is preferably used in terms of copolymerizability.
[0053] The content of the carboxyl group-containing monomer in the polymerization components is usually 1% by weight or less, preferably 0.5% by weight or less, and more preferably 0.3% by weight or less. If the content is too high, the adherend tends to be easily altered, and crosslinking tends to proceed before the drying step when forming a pressure-sensitive adhesive sheet, which tends to cause problems in coating properties.
[0054] Examples of the amino group-containing monomer include aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, and N,N-dimethylaminopropyl (meth)acrylate.
[0055] The content of the amino group-containing monomer in the polymerization components is usually 30% by weight or less, preferably 25% by weight or less, and more preferably 20% by weight or less. If the content is too high, crosslinking proceeds before the drying step when forming the adhesive sheet, which tends to cause problems in coatability.
[0056] Examples of the amide group-containing monomer include (meth)acrylamide-based monomers such as ethoxymethyl(meth)acrylamide, n-butoxymethyl(meth)acrylamide, (meth)acryloylmorpholine, dimethyl(meth)acrylamide, diethyl(meth)acrylamide, dimethylaminopropylacrylamide, and (meth)acrylamide N-methylol(meth)acrylamide.
[0057] The content of the amide group-containing monomer in the polymerization components is usually 30% by weight or less, preferably 25% by weight or less, and more preferably 20% by weight or less. If the content is too high, crosslinking may proceed before the drying step when forming the adhesive sheet, which may cause problems in the coatability.
[0058] Examples of the glycidyl group-containing monomer include glycidyl methacrylate and allyl glycidyl methacrylate.
[0059] The content of the glycidyl group-containing monomer in the polymerization components is usually 1% by weight or less, preferably 0.5% by weight or less, and more preferably 0.3% by weight or less. If the content is too high, crosslinking will proceed before the drying step when forming the adhesive sheet, which tends to cause problems in coating properties.
[0060] Examples of the sulfonic acid group-containing monomer include olefin sulfonic acids such as ethylene sulfonic acid, allyl sulfonic acid, and methallyl sulfonic acid, 2-acrylamido-2-methylolpropane sulfonic acid, styrene sulfonic acid, and salts thereof.
[0061] The content of the sulfonic acid group-containing monomer in the polymerization components is usually 1% by weight or less, preferably 0.5% by weight or less, and more preferably 0.3% by weight or less. If the content is too high, crosslinking will proceed before the drying step in making the adhesive sheet, which tends to cause problems in coating properties.
[0062] Examples of the acetoacetyl group-containing monomer include 2-(acetoacetoxy)ethyl (meth)acrylate and allyl acetoacetate.
[0063] The content of the acetoacetyl group-containing monomer in the polymerization components is usually 10% by weight or less, preferably 5% by weight or less, and more preferably 1% by weight or less. If the content is too high, crosslinking may proceed before the drying step in preparing the adhesive sheet, which may cause problems in coating properties.
[0064] Examples of the other copolymerizable monomers (α3) include vinyl carboxylate ester monomers such as vinyl acetate, vinyl propionate, vinyl stearate, and vinyl benzoate; aromatic ring-containing monomers such as phenyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenyldiethylene glycol (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, styrene, and α-methylstyrene; biphenyloxy structure-containing (meth)acrylic acid ester monomers such as biphenyloxyethyl (meth)acrylate; 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, and the like. acrylate, methoxydiethylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, polypropylene glycol mono(meth)acrylate, and other monomers containing an alkoxy group or an oxyalkylene group; acrylonitrile, methacrylonitrile, vinyl chloride, vinylidene chloride, alkyl vinyl ether, vinyl toluene, vinylpyridine, vinylpyrrolidone, itaconic acid dialkyl ester, fumaric acid dialkyl ester, allyl alcohol, acrylic chloride, methyl vinyl ketone, allyl trimethyl ammonium chloride, dimethyl allyl vinyl ketone, and the like. These may be used alone or in combination of two or more.
[0065] The content of the other copolymerizable monomer (α3) in the polymerization components is usually 40% by weight or less, preferably 30% by weight or less, more preferably 25% by weight or less. If the content of the other copolymerizable monomer (α3) is too high, the adhesive strength tends to decrease.
[0066] The (meth)acrylic resin is produced by polymerizing the above-mentioned (meth)acrylic acid alkyl ester monomer (α1), functional group-containing monomer (α2), and other copolymerizable monomer (α3) as copolymerization components, and such polymerization method can be appropriately carried out by a conventionally known method such as solution radical polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc. Among them, production by solution radical polymerization is preferred in that an acrylic resin can be safely and stably produced with any monomer composition.
[0067] In the solution radical polymerization, for example, monomer components such as a (meth)acrylic acid alkyl ester monomer (α1), a functional group-containing monomer (α2), other copolymerizable monomers (α3), and a polymerization initiator are mixed or dropped into an organic solvent, and polymerization is carried out under reflux or at a temperature of usually 50 to 98° C. for about 0.1 to 20 hours.
[0068] Examples of the organic solvent used in the solution radical polymerization include aromatic hydrocarbons such as toluene and xylene, aliphatic hydrocarbons such as hexane, esters such as ethyl acetate and butyl acetate, aliphatic alcohols such as n-propyl alcohol and isopropyl alcohol, and ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone.
[0069] As the polymerization initiator, a conventional radical polymerization initiator can be used. Specific examples of the polymerization initiator include azo-based polymerization initiators such as azobisisobutyronitrile and azobisdimethylvaleronitrile, and peroxide-based polymerization initiators such as benzoyl peroxide, lauroyl peroxide, di-tert-butyl peroxide and cumene hydroperoxide.
[0070] By the above polymerization method, an acrylic resin, which is one of the preferred embodiments of the polymer (A), can be obtained.
[0071] The polymer (A) such as the polyester resin or acrylic resin explained above preferably has the following physical properties.
[0072] The glass transition temperature (TgA) of the polymer (A) is, from the viewpoint of adhesive properties, usually −70 to 40° C., preferably −50 to 35° C., more preferably −40 to 30° C., even more preferably −30 to 25° C., particularly preferably −25 to 20° C., especially preferably −20 to 15° C., and most preferably −10 to 10° C. If the glass transition temperature (TgA) is too high, flexibility is lost, initial adhesive strength decreases, adhesive strength is difficult to exert even with pressure of the order of finger pressure, and workability tends to decrease, whereas if it is too low, cohesive strength decreases and chemical resistance tends to decrease.
[0073] Here, the glass transition temperature (TgA) of the polymer (A) is a value measured using a differential scanning calorimeter DSC Q20 manufactured by TA Instruments when the polymer (A) is a polyester resin. The measurement temperature range is −90 to 100° C., and the temperature rise rate is 10° C. / min.
[0074] When the polymer (A) is an acrylic resin, the glass transition temperature and weight fraction of each monomer constituting the acrylic resin as a homopolymer are calculated by applying the following Fox formula. TIFF0007615709000001.tif75135Here, the glass transition temperature when the monomers constituting the acrylic resin are made into a homopolymer is usually measured by a differential scanning calorimeter (DSC) and can be measured by a method in accordance with JIS K 7121-1987 or JIS K 6240.
[0075] From the viewpoint of adhesive properties, the glass transition temperature (TgA) of the polymer (A) is preferably higher than the glass transition temperature (TgB) of the polyester resin (B) described below. Furthermore, the glass transition temperature of the polymer (A) is more preferably 5 to 80°C higher than the glass transition temperature of the polyester resin (B), further preferably 10 to 60°C higher, particularly preferably 20 to 40°C higher, and particularly preferably 25 to 35°C higher.
[0076] When the polymer (A) is a polyester resin, the weight average molecular weight is usually 5,000 to 300,000 in terms of the cohesive strength of the adhesive. It is preferably 8,000 to 200,000, particularly preferably 10,000 to 150,000, and further preferably 20,000 to 100,000. If the weight average molecular weight is too small, the adhesive cannot obtain sufficient cohesive strength, and the heat resistance and mechanical strength tend to be easily reduced. If the weight average molecular weight is too large, the adhesion to the substrate tends to be reduced.
[0077] The weight average molecular weight of the polyester resin is a weight average molecular weight converted into a standard polystyrene molecular weight, and is measured using a high performance liquid chromatograph (manufactured by Waters, "ACQUITY APC System") equipped with four columns in series: one ACQUITY APC XT 450, one ACQUITY APC XT 200, and two ACQUITY APC XT 45.
[0078] When the polymer (A) is an acrylic resin, the weight average molecular weight is usually 200,000 to 1,500,000 from the viewpoint of the cohesive strength of the adhesive. It is preferably 300,000 to 1,000,000, and particularly preferably 400,000 to 800,000. If the weight average molecular weight is too small, the adhesive cannot obtain sufficient cohesive strength, and the heat resistance and mechanical strength tend to be easily reduced. If the weight average molecular weight is too large, the adhesion to the substrate tends to be reduced.
[0079] The weight-average molecular weight of the above acrylic resin was measured using a high-performance liquid chromatograph (Waters Japan, "Waters 2695 (main unit)" and "Waters 2414 (detector)") with a Shodex GPC KF-806L column (exclusion limit molecular weight: 2 × 10 7 , Separation range: 100~2×10 7 The measurement is performed using three columns in series (theoretical plate number: 10,000 plates / column, filler material: styrene-divinylbenzene copolymer, filler particle size: 10 μm).
[0080] The hydroxyl value of the polymer (A) is preferably 50 mgKOH / g or less, more preferably 30 mgKOH / g or less, further preferably 20 mgKOH / g or less, and particularly preferably 15 mgKOH / g or less. If the hydroxyl value is too high, the crosslinking efficiency with the crosslinking agent (D) tends to decrease.
[0081] The acid value of the polymer (A) is preferably 10 mgKOH / g or less, more preferably 5 mgKOH / g or less, even more preferably 3 mgKOH / g or less, particularly preferably 1 mgKOH / g or less, and especially preferably 0.5 mgKOH / g or less. If the acid value is too high, hydrolysis tends to proceed easily, and when a layer such as a metal is attached to one side of the pressure-sensitive adhesive layer, corrosion tends to occur.
[0082] The hydroxyl value and acid value in the present invention are determined by neutralization titration based on JIS K0070.
[0083] <Polyester resin (B)> The polyester resin (B) exhibits an effect as a tackifier, has a structural unit derived from a polyvalent carboxylic acid (b1) and a structural unit derived from a polyol (b2), and has at least one reactive molecular end blocked, and the reactive molecular end is preferably blocked with a blocking agent (b3). In addition, it is preferable that at least one of the structural unit derived from the polyvalent carboxylic acids (b1), the structural unit derived from the polyol (b2), and the blocking agent (b3) contains an aromatic structural unit in terms of excellent chemical resistance, it is more preferable that the structural unit derived from the polyvalent carboxylic acids (b1) and / or the blocking agent (b3) contains an aromatic structural unit, and it is particularly preferable that the blocking agent (b3) contains an aromatic structural unit.
[0084] The polyester resin (B) is obtained by blocking the reactive molecular ends of a polyester resin (B') before end blocking, which has at least one of a carboxyl group end derived from a polyvalent carboxylic acid (b1) and a hydroxyl group end derived from a polyol (b2) as reactive molecular ends, with a blocking agent (b3) described later. The polyester resin (B') before end-capping will be described below.
[0085] [Polyester resin (B') before end blocking] The polyester resin (B') before the terminal blocking (hereinafter, sometimes referred to as "polyester resin (B')") is usually obtained by copolymerizing copolymerization components containing polyvalent carboxylic acids (b1) and polyol (b2) as constituent raw materials, and the polyester resin (B') has, as its resin composition, structural units derived from the polyvalent carboxylic acids (b1) and structural units derived from the polyol (b2).
[0086] [Structural units derived from polyvalent carboxylic acids (b1)] Examples of the structural unit derived from the polyvalent carboxylic acid (b1) include those explained above as the structural unit derived from the polyvalent carboxylic acid (a1).
[0087] Among the structural units derived from the polyvalent carboxylic acids (b1), from the viewpoint of reducing the crystallinity of the polyester resin and from the viewpoint of excellent chemical resistance, it is preferable to include structural units derived from aromatic polyvalent carboxylic acids, particularly structural units derived from asymmetric aromatic dicarboxylic acids (b1-1), and examples of structural units derived from asymmetric aromatic dicarboxylic acids (b1-1) include structural units derived from phthalic acids, isophthalic acids, 1,8-naphthalenedicarboxylic acids, 2,3-naphthalenedicarboxylic acids, and 2,7-naphthalenedicarboxylic acids. Among them, structural units derived from isophthalic acids are particularly preferable from the viewpoint of reactivity.
[0088] The content of the structural units derived from such aromatic polycarboxylic acids, particularly the structural units derived from asymmetric aromatic dicarboxylic acids (b1-1), is preferably 0.1 to 100 mol%, more preferably 5 to 80 mol%, even more preferably 10 to 70 mol%, and particularly preferably 20 to 60 mol%, based on the total structural units derived from polycarboxylic acids (b1). If the content is too low, the chemical resistance tends to decrease, or the polyester resin (B) tends to crystallize, making it difficult to obtain sufficient adhesive performance, and if the content is too high, the initial adhesive strength (tack) tends to decrease. Note that, if the content is within the preferred range, the initial adhesive strength (tack) tends to be excellent.
[0089] In addition, from the viewpoint of improving the initial adhesive strength (tack), the structural unit derived from the polyvalent carboxylic acids (b1) preferably contains a structural unit derived from an aliphatic dicarboxylic acid (b1-2) having 4 or more carbon atoms (including the carbon of the carboxy group), more preferably contains a structural unit derived from an aliphatic dicarboxylic acid having 6 to 12 carbon atoms (including the carbon of the carboxy group), and particularly preferably contains a structural unit derived from an adipic acid, a sebacic acid, or an azelaic acid.
[0090] The content of the structural units derived from the aliphatic dicarboxylic acids (b1-2) having 4 or more carbon atoms is preferably 10 to 100 mol % based on the total structural units derived from the polyvalent carboxylic acids (b1). In particular, it is preferably 20 to 95 mol %, more preferably 30 to 90 mol %, and particularly preferably 40 to 80 mol %. If the content is too low, the glass transition temperature of the polyester resin (B) becomes too high, and sufficient adhesive strength tends to be difficult to obtain. Note that, if the content is within the preferred range, crystallization of the polyester resin (B) is suppressed, and the initial adhesive strength of the adhesive tends to be excellent.
[0091] In the present invention, from the viewpoint of adhesive properties, it is also preferable to contain, as the structural units derived from polyvalent carboxylic acids (b1), structural units derived from asymmetric aromatic dicarboxylic acids (b1-1) and structural units derived from aliphatic dicarboxylic acids (b1-2) having 4 or more carbon atoms. In this case, the content ratio (molar ratio) of the structural units derived from asymmetric aromatic dicarboxylic acids (b1-1) and the structural units derived from aliphatic dicarboxylic acids (b1-2) having 4 or more carbon atoms is preferably (b1-1) / (b1-2)=1 / 99 to 99 / 1, particularly preferably 5 / 95 to 90 / 10, further preferably 20 / 80 to 80 / 20, and particularly preferably 30 / 70 to 70 / 30.
[0092] In addition, in order to increase the number of branching points in the polyester resin, structural units derived from trivalent or higher polyvalent carboxylic acids (b1-3) can also be used, and among these, it is preferable to use trimellitic acids, since they are relatively unlikely to cause gelation during production.
[0093] The content of the structural units derived from such trivalent or higher polyvalent carboxylic acids (b1-3) is preferably 10 mol % or less, particularly preferably 0.1 to 5 mol %, based on the total amount of the polyvalent carboxylic acids (b1), in order to increase the cohesive strength when used as an adhesive. If the content is too high, gelation tends to occur easily during production of the polyester resin.
[0094] [Polyol (b2)] Examples of the structural unit derived from the polyol (b2) include those explained above as the structural unit derived from the polyol (a2).
[0095] As the structural unit derived from the above polyol (b2), from the viewpoint of lowering the glass transition temperature (TgB) of the polyester resin (B) and improving the initial adhesive strength, it is preferable that it contains a structural unit derived from an aliphatic diol (b2-1) having a linear structure, more preferably contains a structural unit derived from an aliphatic diol having 2 to 18 carbon atoms, and particularly preferably contains a structural unit derived from 1,6-hexanediol.
[0096] The content of the structural unit derived from the linear aliphatic diol (b2-1) is preferably 1 to 100 mol%, more preferably 5 to 90 mol%, further preferably 10 to 80 mol%, particularly preferably 15 to 70 mol%, and particularly preferably 20 to 60 mol%, based on the total structural units derived from the polyol (b2). If the content is too low, the reactivity during the production of the polyester resin (B') tends to decrease. If the content is within the preferred range, the crystallization of the polyester resin (B) is suppressed, and the initial adhesive strength of the adhesive tends to be excellent.
[0097] Among the structural units derived from the polyol (b2), it is preferable to contain a structural unit derived from a diol (b2-2) having a hydrocarbon group in the side chain, because it can break the crystallinity. Examples of the structural units derived from the diol (b2-2) having a hydrocarbon group include those described for the diol (a2-2) having a hydrocarbon group. Among them, it is preferable to contain a structural unit derived from an aliphatic diol having a branched structure, and it is particularly preferable to contain a structural unit derived from 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), or 3-methyl-1,5-pentanediol.
[0098] The content of the structural unit derived from the diol (b2-2) having a hydrocarbon group in the side chain is preferably 5 to 100 mol %, particularly preferably 15 to 80 mol %, and further preferably 30 to 70 mol %, based on the total structural units derived from the polyol (b2). If the content is too low, the polyester resin (B) tends to crystallize, and the initial adhesive strength of the adhesive tends to decrease. If the content is within the preferred range, the reactivity of the polyester resin (B') during production tends to be high.
[0099] Furthermore, the structural units derived from the polyol (b2) may contain structural units derived from a trivalent or higher polyol (b2-3). The content of the structural units derived from the trivalent or higher polyol (b2-3) is preferably 10 mol% or less, more preferably 0.01 to 5 mol%, particularly preferably 0.05 to 3 mol%, and particularly preferably 0.1 to 1 mol%, based on the total structural units derived from the polyol (b2). If the content of the structural units derived from the trivalent or higher polyol (b2-3) is too high, the tackiness tends to decrease.
[0100] The above polyvalent carboxylic acids (b1) and polyol (b2) are reacted in a manner similar to the above-mentioned method for producing a polyester resin, to obtain a polyester resin (B') before end-capping.
[0101] In addition, the blending ratio of the polyvalent carboxylic acid (b1) and the polyol (b2) in the polyester resin (B') is preferably 1 to 2 equivalents of the polyol (b2) per equivalent of the polyvalent carboxylic acid (b1) in the case of a polyester resin (B') having a hydroxyl group terminal, particularly preferably 1.03 to 1.8 equivalents, more preferably 1.05 to 1.7, and particularly preferably 1.1 to 1.6. If the blending ratio of the polyol (b2) is too low, the compatibility with the polymer (A) tends to decrease, and if it is too high, the cohesive force of the adhesive tends to decrease and the chemical resistance tends to decrease. In the case of a polyester resin (B') having a carboxy terminus, the polyvalent carboxylic acid (b1) is preferably 1 to 2 equivalents per equivalent of the polyol (b2), particularly preferably 1.03 to 1.8 equivalents, more preferably 1.05 to 1.7, and particularly preferably 1.1 to 1.6. If the blending ratio of the polyvalent carboxylic acid (b1) is too low, the compatibility with the polymer (A) tends to decrease, whereas if it is too high, the cohesive strength of the adhesive tends to decrease, resulting in decreased chemical resistance.
[0102] The polyester resin (B') thus obtained typically has, as reactive molecular ends, at least one of a carboxyl group end derived from the polyvalent carboxylic acid (b1) and a hydroxyl group end derived from the polyol (b2), and from the viewpoint of hydrolysis resistance, it is more preferable that the polyester resin (B') has a hydroxyl group end.
[0103] The glass transition temperature (Tg) of the polyester resin (B') is usually -80 to 30°C, preferably -75 to 20°C, more preferably -70 to 0°C, particularly preferably -65 to -20°C, and especially preferably -60 to -40°C, from the viewpoint of adhesive properties. If the glass transition temperature (Tg) is too high, flexibility is lost, initial adhesive strength is reduced, adhesive strength is difficult to exert with pressure of the finger pressure, and workability tends to decrease, whereas if the glass transition temperature is too low, cohesive strength is reduced, and the adhesive sheet tends to be easily deformed, resulting in impaired appearance. The glass transition temperature of the polyester resin (B') can be measured by the same method as that of the polyester resin described for the polymer (A).
[0104] In addition, the number average molecular weight of the polyester resin (B') is usually 200 to 30,000, preferably 500 to 20,000, particularly preferably 1,000 to 10,000, further preferably 1,000 to 9,000, particularly preferably 1,500 to 8,000, and more preferably 2,000 to 6,000, from the viewpoint of the cohesive strength of the adhesive. If the number average molecular weight is too small, the adhesive cannot obtain sufficient cohesive strength, and the heat resistance and mechanical strength tend to be easily reduced. If the number average molecular weight is too large, the compatibility with the polymer (A) tends to be reduced. The number average molecular weight can be measured by the same method as the weight average molecular weight of the polyester resin described in the polymer (A).
[0105] The hydroxyl value of the polyester resin (B') is 5 to 200 mgKOH / g, preferably 10 to 150 mgKOH / g, more preferably 15 to 100 mgKOH / g, when the polyester resin (B') has a terminal hydroxyl group. If the hydroxyl value is too high, the cohesive strength tends to decrease, whereas if the hydroxyl value is too low, the compatibility with the polymer (A) tends to decrease. In addition, in the case of a polyester resin (B') having a carboxyl group terminal, the hydroxyl value is 10 mgKOH / g or less, preferably 5 mgKOH / g or less, more preferably 3 mgKOH / g or less, particularly preferably 1 mgKOH / g or less, and especially preferably 0.5 mgKOH / g or less. The lower limit is 0.0 mgKOH / g. If the hydroxyl value is too high, the tackiness tends to decrease.
[0106] The acid value of the polyester resin (B') is 10 mgKOH / g or less, preferably 5 mgKOH / g or less, more preferably 3 mgKOH / g or less, particularly preferably 1 mgKOH / g or less, and especially preferably 0.5 mgKOH / g or less, when the polyester resin (B') has a hydroxyl group terminal. The lower limit is 0.0 mgKOH / g. If the acid value is too high, the cohesive strength decreases and hydrolysis tends to proceed easily. In the case of a polyester resin (B') having a terminal carboxy group, the acid value is 5 to 200 mgKOH / g, preferably 10 to 150 mgKOH / g, and more preferably 15 to 100 mgKOH / g. If the acid value is too high, the cohesive strength tends to decrease, hydrolysis tends to proceed easily, and when a layer of metal or the like is laminated on one side of the pressure-sensitive adhesive layer, corrosion tends to occur.
[0107] As described above, the polyester resin (B') generally has at least one of a carboxyl group terminal and a hydroxyl group terminal as a reactive molecular end. The polyester resin (B) used in the present invention is obtained by blocking at least one of the reactive molecular ends of the polyester resin (B') with a blocking agent (b3).
[0108] [Sequestering agent (b3)] The blocking agent (b3) contains a functional group reactive with the reactive terminal of the polyester resin (B'), and examples thereof include isocyanate group-containing compounds, carbodiimide group-containing compounds, epoxy group-containing compounds, oxazoline group-containing compounds, carboxy group-containing compounds, hydroxy group-containing compounds, etc. These may be used alone or in combination of two or more kinds.
[0109] In the present invention, the isocyanate group-containing compound is preferably a monoisocyanate having one isocyanate group in the molecular structure. Examples of the monoisocyanate compound include aliphatic monoisocyanate compounds such as methyl isocyanate, ethyl isocyanate, propyl isocyanate, n-butyl isocyanate, t-butyl isocyanate, isobutyl isocyanate, pentyl isocyanate, neopentyl isocyanate, 2-ethyl-hexyl isocyanate, 2-isocyanatoethyl methacrylate, 2-isocyanatoethyl acrylate, and octadecyl isocyanate, and aromatic monoisocyanate compounds such as phenyl isocyanate, tolyl isocyanate, 1-naphthyl isocyanate, 2-naphthyl isocyanate, and m-isopropenyl-α,α-dimethylbenzyl isocyanate. These may be used alone or in combination of two or more. Among them, aromatic monoisocyanate compounds are preferred in terms of excellent reactivity and chemical resistance, and phenyl isocyanate is particularly preferred.
[0110] In the present invention, the carbodiimide group-containing compound is preferably a monocarbodiimide having one carbodiimide group (-N=C=N-) in the molecule. Examples of the monocarbodiimide compound include dicyclohexylcarbodiimide, diisopropylcarbodiimide, dimethylcarbodiimide, diisobutylcarbodiimide, dioctylcarbodiimide, diphenylcarbodiimide, and naphthylcarbodiimide, etc. These may be used alone or in combination of two or more kinds.
[0111] In the present invention, the epoxy group-containing compound is preferably a monofunctional epoxy compound having one epoxy group in the molecular structure, such as a monoglycidyl ester compound, a monoglycidyl ether compound, etc. These may be used alone or in combination of two or more kinds.
[0112] Examples of the monoglycidyl ester compound include benzoic acid glycidyl ester, t-Bu-benzoic acid glycidyl ester, p-toluic acid glycidyl ester, cyclohexane carboxylic acid glycidyl ester, pelargonic acid glycidyl ester, stearic acid glycidyl ester, lauric acid glycidyl ester, palmitic acid glycidyl ester, behenic acid glycidyl ester, versatic acid glycidyl ester, oleic acid glycidyl ester, linoleic acid glycidyl ester, linolenic acid glycidyl ester, behenolic acid glycidyl ester, stearolic acid glycidyl ester, and the like. These can be used alone or in combination of two or more kinds.
[0113] Examples of the monoglycidyl ether compound include phenyl glycidyl ether, o-phenyl glycidyl ether, and the like, which can be used alone or in combination of two or more kinds.
[0114] In the present invention, the oxazoline group-containing compound is preferably a monofunctional oxazoline compound having one oxazoline group in the molecular structure.Specific examples include 2-phenyl(2-oxazoline), 2-ethyl-2-oxazoline, etc., which can be used alone or in combination of two or more.
[0115] In the present invention, the carboxy group-containing compound is preferably a monocarboxylic acid having one carboxy group in the molecular structure, and particularly preferably a saturated monocarboxylic acid. Examples of the monocarboxylic acid include aliphatic monocarboxylic acids such as formic acid, acetic acid, propionic acid, butyric acid, isobutyric acid, valeric acid, isovaleric acid, 2-methylbutanoic acid, pivalic acid, hexanoic acid, 4-methylpentanoic acid, 2-ethylbutanoic acid, 2,2-dimethylbutanoic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, undecanoic acid, dodecanoic acid, tridecanoic acid, tetradecanoic acid, pentadecanoic acid, hexadecanoic acid, heptadecanoic acid, octadecanoic acid, eicosanoic acid, docosanoic acid, hexacosanoic acid, and triacontanoic acid, and aromatic monocarboxylic acids such as benzoic acid, toluic acid, naphthalene carboxylic acid, methylnaphthalene carboxylic acid, and phenyl acetic acid, and these can be used alone or in combination of two or more.Among these, aromatic monocarboxylic acids are preferred in terms of excellent reactivity and chemical resistance.
[0116] In the present invention, the hydroxy group-containing compound is preferably a monoalcohol having one hydroxy group in the molecular structure. Examples of the monoalcohol include aliphatic monoalcohols such as butanol, hexanol, pentanol, heptanol, octanol, nonanol, decanol, undecanol, dodecanol, and tridecanol, and aromatic monoalcohols such as benzyl alcohol and 3-phenyl-1-propanol. These can be used alone or in combination of two or more kinds.
[0117] In the present invention, in addition to the compounds having one functional group as described above, compounds having two or more functional groups can also be used as the blocking agent (b3) within a range that does not impair the effects of the present invention.
[0118] Among the blocking agents (b3), isocyanate group-containing compounds are preferred because they have excellent reactivity with the hydroxyl group terminals of the polyester resin (B').
[0119] In addition, from the viewpoint of excellent adhesive properties, the blocking agent (b3) preferably has a number average molecular weight of 50 to 5000, more preferably 60 to 3000, particularly preferably 70 to 1000, further preferably 80 to 500, and particularly preferably 90 to 300. If the molecular weight is too small, the volatility tends to be high, and if it is too large, the compatibility with the polymer (A) tends to be reduced.
[0120] In view of excellent adhesive properties, the polyester resin (B) used in the present invention is preferably one in which at least one reactive molecular end is blocked with the blocking agent (b3), and more preferably, all reactive molecular ends are blocked.
[0121] The blocking of the reactive molecular ends of the polyester resin (B') using the blocking agent (b3) may be carried out by a known method, for example, by reacting the polyester resin (B') with the blocking agent (b3) in an organic solvent.
[0122] The reaction ratio of the polyester resin (B') and the blocking agent (b3) is preferably optimized according to the hydroxyl value and acid value of the polyester resin (B'), i.e., according to the carboxyl groups and hydroxyl groups of the polyester resin (B'). For 100 mol % of the carboxyl groups or 100 mol % of the hydroxyl groups of the polyester resin (B'), the functional groups that react with the reactive molecular terminals of the blocking agent (b3) may be used in an amount of usually 80 to 120 mol %, preferably 90 to 110 mol %, more preferably 95 to 105 mol %, particularly preferably 97 to 103 mol %, even more preferably 98 to 102 mol %, and especially preferably 99 to 101 mol %. For example, when an isocyanate group-containing compound is used as the blocking agent (b3), since the isocyanate group-containing compound is reactive with carboxy groups and hydroxy groups, the isocyanate group-containing compound may be used in the above range relative to the total of 100 mol % of the carboxy groups and hydroxy groups contained in the polyester resin (B').
[0123] The organic solvent may be one that does not show reactivity with the blocking agent (b3), and may be, for example, an ester such as ethyl acetate or butyl acetate, a ketone such as methyl ethyl ketone or methyl isobutyl ketone, an aromatic such as toluene or xylene, etc. These may be used alone or in combination of two or more kinds.
[0124] The reaction temperature between the polyester resin (B') and the blocking agent (b3) is usually 20 to 80°C, preferably 30 to 60°C, and the reaction time is usually 0.1 to 24 hours, preferably 0.5 to 12 hours, more preferably 0.5 to 3 hours.
[0125] By the above method, a polyester resin (B) having at least one reactive molecular end blocked can be obtained.
[0126] The glass transition temperature (TgB) of the polyester resin (B) is preferably -80 to 30°C, more preferably -70 to 25°C, even more preferably -60 to 20°C, particularly preferably -55 to 0°C, particularly preferably -50 to -10°C, and most preferably -40 to -15°C. If the glass transition temperature of the polyester resin (B) is too low, the cohesive strength tends to decrease and the chemical resistance tends to decrease, and if the glass transition temperature is too high, the flexibility tends to be lost, the initial adhesive strength tends to decrease, and the adhesive strength tends to be difficult to exert with a pressure of about finger pressure. As already mentioned, in relation to the glass transition temperature of the polymer (A), the glass transition temperature (TgA) of the polymer (A) is preferably higher than the glass transition temperature (TgB) of the polyester resin (B).
[0127] The polyester resin (B) is preferably amorphous. If it is crystalline, the heat of fusion of crystal is preferably 20 J / g or less, more preferably 10 J / g or less, particularly preferably 5 J / g or less, even more preferably 3 J / g or less, and particularly preferably 1 J / g or less. If the heat of fusion of crystal is too high, the storage stability and tackiness tend to decrease, and the compatibility with the polymer (A) tends to be poor.
[0128] Here, the crystalline heat of fusion of the polyester resin (B) is a value measured using a differential scanning calorimeter DSC Q20 manufactured by TA Instruments. The measurement temperature range was -90 to 100°C, and the temperature increase rate was 10°C / min. The heat of fusion heat generated when the sample was heated to 100°C for complete melting, cooled to -90°C, and then heated again to 100°C was defined as the heat of fusion of crystals.
[0129] The number average molecular weight of the polyester resin (B) is 300 to 30,000 in terms of the cohesive strength of the adhesive. It is preferably 500 to 20,000, particularly preferably 1,000 to 10,000, further preferably 1,000 to 8,000, particularly preferably 1,500 to 6,000, and more preferably 2,000 to 4,000. If the number average molecular weight is too small, the polyester resin (B) used as a tackifier does not provide sufficient cohesive strength as an adhesive, and the heat resistance and mechanical strength tend to be easily reduced. If the number average molecular weight is too large, the compatibility with the polymer (A) tends to be reduced. The number average molecular weight can be measured by the same method as the weight average molecular weight of the polyester resin described in the polymer (A).
[0130] The hydroxyl value of the polyester resin (B) is preferably 10 mgKOH / g or less, more preferably 8 mgKOH / g or less, even more preferably 5 mgKOH / g or less, particularly preferably 3 mgKOH / g or less, particularly preferably 1 mgKOH / g or less, and most preferably 0.5 mgKOH / g or less. The lower limit is 0 mgKOH / g. If the hydroxyl value is too high, crosslinking with the polymer (A) tends to reduce the adhesive strength and tackiness.
[0131] The acid value of the polyester resin (B) is preferably 10 mgKOH / g or less, more preferably 5 mgKOH / g or less, even more preferably 3 mgKOH / g or less, particularly preferably 1 mgKOH / g or less, and especially preferably 0.5 mgKOH / g or less. The lower limit is 0 mgKOH / g. If the acid value is too high, crosslinking with the polymer (A) tends to reduce adhesion and tackiness, and hydrolysis resistance tends to decrease.
[0132] The total acid value and hydroxyl value of the polyester resin (B) is preferably 15 mgKOH / g or less, more preferably 10 mgKOH / g or less, even more preferably 5 mgKOH / g or less, particularly preferably 3 mgKOH / g or less, particularly preferably 1 mgKOH / g or less, and most preferably 0.5 mgKOH / g or less. The lower limit is 0 mgKOH / g. If the total acid value and hydroxyl value is too high, crosslinking with the polymer (A) tends to reduce adhesion and tackiness, or reduce hydrolysis resistance.
[0133] The content of the polyester resin (B) is preferably 0.1 to 180 parts by weight, more preferably 1 to 175 parts by weight, even more preferably 5 to 170 parts by weight, particularly preferably 10 to 160 parts by weight, more preferably 30 to 150 parts by weight, even more preferably 40 to 140 parts by weight, particularly preferably 50 to 130 parts by weight, particularly preferably 60 to 120 parts by weight, and most preferably 70 to 110 parts by weight, relative to 100 parts by weight of the polymer (A). If the content of the polyester resin (B) is too high, the cohesive force tends to decrease and the chemical resistance tends to decrease, and if the content is too low, the tackiness tends to decrease.
[0134] The content of the polyester resin (B) is preferably 0.1 to 75% by weight, more preferably 1 to 70% by weight, even more preferably 5 to 65% by weight, particularly preferably 10 to 60% by weight, especially preferably 20 to 55% by weight, and most preferably 30 to 50% by weight, relative to 100% by weight of the adhesive composition. If the content of the polyester resin (B) is too high, the cohesive strength and chemical resistance tend to decrease, whereas if the content is too low, the tackiness tends to decrease.
[0135] <Hydrolysis inhibitor (C)> The pressure-sensitive adhesive composition of the present invention preferably further contains a hydrolysis inhibitor (C) for the purpose of ensuring long-term durability.
[0136] As the hydrolysis inhibitor (C), a conventionally known one can be used, for example, a compound that reacts with the carboxyl group terminal of the polymer (A) and bonds thereto, specifically, for example, a compound containing a functional group such as a carbodiimide group, an epoxy group, or an oxazoline group. The hydrolysis inhibitor (C) can be used alone or in combination of two or more kinds. Among them, a carbodiimide group-containing compound is preferred because it has a high effect of eliminating the catalytic activity of the proton derived from the carboxylic acid terminal group.
[0137] The carbodiimide group-containing compound is usually a known carbodiimide compound having one or more carbodiimide groups (-N=C=N-) in the molecule, and among them, a compound having two or more carbodiimide groups in the molecule, i.e., a polyvalent carbodiimide compound, is preferable, and particularly a compound having three or more, further five or more, and especially seven or more carbodiimide groups in the molecule is preferable. The number of carbodiimide groups contained in the molecule of the polyvalent carbodiimide compound is usually 50 or less, and if there are too many carbodiimide groups, the molecular structure becomes too large, which tends to reduce the compatibility with the polymer (A), which is not preferable.
[0138] As the carbodiimide group-containing compound, it is also preferable to use a high molecular weight polycarbodiimide produced by subjecting a diisocyanate to a decarboxylation condensation reaction in the presence of a carbodiimide catalyst.
[0139] Such high molecular weight polycarbodiimides may be synthesized or commercially available products may be used. When synthesizing high molecular weight polycarbodiimides, for example, those obtained by subjecting the following diisocyanates to a decarboxylation condensation reaction may be used.
[0140] Examples of such diisocyanates include 4,4'-diphenylmethane diisocyanate, 3,3'-dimethoxy-4,4'-diphenylmethane diisocyanate, 3,3'-dimethyl-4,4'-diphenylmethane diisocyanate, 4,4'-diphenylether diisocyanate, 3,3'-dimethyl-4,4'-diphenylether diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 1-methoxyphenyl-2,4-diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, tetramethylxylylene diisocyanate, and the like. These can be used alone or in combination of two or more.
[0141] Furthermore, the high molecular weight polycarbodiimide is preferably one in which the terminal isocyanate group is blocked with a blocking agent from the viewpoint of storage stability. Examples of blocking agents include compounds having active hydrogen that reacts with isocyanate groups, or compounds having isocyanate groups. Examples of blocking agents include monoalcohols, monocarboxylic acids, monoamines, and monoisocyanates having one substituent selected from carboxyl groups, amino groups, and isocyanate groups.
[0142] The carbodiimide equivalent of the carbodiimide group-containing compound is preferably 50-10,000, particularly preferably 100-1,000, and further preferably 150-500. The carbodiimide equivalent weight refers to the chemical formula weight per one carbodiimide group.
[0143] The carbodiimide group-containing compound may be a commercially available product. Examples of commercially available carbodiimide group-containing compounds include the Carbodilite (registered trademark) series manufactured by Nisshinbo Chemical Inc. Among these, Carbodilite (registered trademark) "V-01", "V-02B", "V-03", "V-04K", "V-04PF", "V-05", "V-07", "V-09", and "V-09GB" are preferred in that they have excellent compatibility with the polymer (A).
[0144] Examples of the epoxy group-containing compound include glycidyl ester compounds, glycidyl ether compounds, etc. These can be used alone or in combination of two or more kinds. Examples of the glycidyl ester compound include benzoic acid glycidyl ester, t-Bu-benzoic acid glycidyl ester, p-toluic acid glycidyl ester, cyclohexane carboxylic acid glycidyl ester, pelargonic acid glycidyl ester, stearic acid glycidyl ester, lauric acid glycidyl ester, palmitic acid glycidyl ester, behenic acid glycidyl ester, versatic acid glycidyl ester, oleic acid glycidyl ester, linoleic acid glycidyl ester, linolenic acid glycidyl ester, behenolic acid glycidyl ester, stearolic acid glycidyl ester, terephthalic acid diglycidyl ester, isophthalic acid diglycidyl ester, Examples of the glycidyl ester include diglycidyl ester of ...
[0145] Examples of the glycidyl ether compound include phenyl glycidyl ether, o-phenyl glycidyl ether, 1,4-bis(β,γ-epoxypropoxy)butane, 1,6-bis(β,γ-epoxypropoxy)hexane, 1,4-bis(β,γ-epoxypropoxy)benzene, 1-(β,γ-epoxypropoxy)-2-ethoxyethane, 1-(β,γ-epoxypropoxy)-2-benzyloxyethane, 2,2-bis-[р-(β,γ-epoxypropoxy)phenyl]propane, and bisglycidyl polyethers obtained by reacting bisphenols such as 2,2-bis-(4-hydroxyphenyl)propane and 2,2-bis-(4-hydroxyphenyl)methane with epichlorohydrin, and the like. These can be used alone or in combination of two or more kinds.
[0146] The oxazoline group-containing compound is preferably a bisoxazoline compound. Specifically, for example, 2,2'-bis(2-oxazoline), 2,2'-bis(4-methyl-2-oxazoline), 2,2'-bis(4,4-dimethyl-2-oxazoline), 2,2'-bis(4-ethyl-2-oxazoline), 2,2'-bis(4,4'-diethyl-2-oxazoline), 2,2'-bis(4-propyl-2-oxazoline), 2,2'-bis(4-butyl-2-oxazoline), 2,2'-bis(4-hexyl-2-oxazoline), 2,2'-bis(4-methyl ... -oxazoline), 2,2'-bis(4-phenyl-2-oxazoline), 2,2'-bis(4-cyclohexyl-2-oxazoline), 2,2'-bis(4-benzyl-2-oxazoline), 2,2'-p-phenylenebis(2-oxazoline), 2,2'-m-phenylenebis(2-oxazoline), 2,2'-o-phenylenebis(2-oxazoline), 2,2'-p-phenylenebis(4-methyl-2-oxazoline), 2,2' -p-phenylenebis(4,4-dimethyl-2-oxazoline), 2,2'-m-phenylenebis(4-methyl-2-oxazoline), 2,2'-m-phenylenebis(4,4-dimethyl-2-oxazoline), 2,2'-ethylenebis(2-oxazoline), 2,2'-tetramethylenebis(2-oxazoline), 2,2'-hexamethylenebis(2-oxazoline), 2,2'-octamethylenebis(2-oxazoline), 2,2' -decamethylenebis(2-oxazoline), 2,2'-ethylenebis(4-methyl-2-oxazoline), 2,2'-tetramethylenebis(4,4-dimethyl-2-oxazoline), 2,2'-9,9'-diphenoxyethanebis(2-oxazoline), 2,2'-cyclohexylenebis(2-oxazoline), 2,2'-diphenylenebis(2-oxazoline), and the like. These can be used alone or in combination of two or more.
[0147] It is preferable that the hydrolysis inhibitor (C) has low volatility, and therefore it is preferable to use one having a high number average molecular weight, usually 300 to 10,000, preferably 1,000 to 5,000. In addition, from the viewpoint of hydrolysis resistance, it is preferable to use a hydrolysis inhibitor (C) having a high weight average molecular weight. The weight average molecular weight of the hydrolysis inhibitor (C) is preferably 500 or more, more preferably 2000 or more, and even more preferably 3000 or more. The upper limit of the weight average molecular weight is usually 50,000. If the molecular weight of the hydrolysis inhibitor (C) is too small, the hydrolysis resistance tends to decrease, whereas if the molecular weight is too large, the compatibility with the polymer (A) tends to decrease.
[0148] The content of the hydrolysis inhibitor (C) is preferably 0.01 to 10 parts by weight, particularly preferably 0.1 to 5 parts by weight, further preferably 0.3 to 3 parts by weight, and particularly preferably 0.5 to 2 parts by weight, based on 100 parts by weight of the polymer (A). If the content is too high, turbidity tends to occur due to poor compatibility with the polymer (A), while if the content is too low, sufficient durability tends to be difficult to obtain.
[0149] It is preferable that the content of the hydrolysis inhibitor (C) is optimized according to the acid value of the polymer (A). For example, when the polymer (A) is a polyester resin, the molar ratio (Y) / (X) of the total number of moles of functional groups of the hydrolysis inhibitor (C) in the pressure-sensitive adhesive composition to the total number of moles of acidic functional groups of the polyester resin in the pressure-sensitive adhesive composition (X) is preferably 0.5≦(Y) / (X), particularly preferably 1≦(Y) / (X)≦1000, and even more preferably 1.5≦(Y) / (X)≦100. If the molar ratio of (Y) to (X) is too low, the moisture and heat resistance tends to decrease, whereas if the molar ratio of (Y) to (X) is too high, the compatibility with the polymer (A) tends to decrease, and the adhesive strength, cohesive strength, and durability tend to decrease.
[0150] <Crosslinking agent (D)> The pressure-sensitive adhesive composition of the present invention preferably further contains a crosslinking agent (D). Examples of the crosslinking agent (D) include compounds having a functional group that reacts with at least one of the hydroxyl group and the carboxyl group contained in the polymer (A), such as polyisocyanate-based compounds and polyepoxy-based compounds. Among these, it is particularly preferable to use polyisocyanate-based compounds, since they can achieve a good balance between the initial adhesive strength, mechanical strength, and heat resistance.
[0151] Examples of such polyisocyanate compounds include polyisocyanates such as tetramethylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, tolylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, tetramethylxylylene diisocyanate, 1,5-naphthalene diisocyanate, and triphenylmethane triisocyanate. In addition, examples of such polyisocyanate compounds include adducts of the above polyisocyanates with polyol compounds such as trimethylolpropane, and biuret and isocyanurate compounds of these polyisocyanate compounds. The above polyisocyanate compounds may also be used in which the isocyanate portion is blocked with phenol, lactam, or the like. These crosslinking agents (D) may be used alone or in combination of two or more.
[0152] The content of the crosslinking agent (D) can be appropriately selected depending on the molecular weight and intended use of the polymer (A). In general, the crosslinking agent (D) is preferably contained in a ratio such that the reactive group contained in the crosslinking agent (D) is 0.2 to 10 equivalents per equivalent of at least one of the hydroxyl group and the carboxy group contained in the polymer (A), particularly preferably 0.5 to 5 equivalents, and further preferably 0.5 to 3 equivalents. If the equivalent number of the reactive groups contained in the crosslinking agent (D) is too small, the cohesive strength tends to decrease, whereas if it is too large, the flexibility tends to decrease.
[0153] The content of the crosslinking agent (D) is preferably 0.1 to 20 parts by weight, more preferably 0.5 to 15 parts by weight, particularly preferably 1 to 10 parts by weight, further preferably 1.5 to 8 parts by weight, and particularly preferably 2 to 6 parts by weight, relative to 100 parts by weight of the polymer (A). If the content of the crosslinking agent (D) is too high, the tackiness tends to decrease, whereas if the content is too low, the cohesive strength and chemical resistance tend to decrease.
[0154] In the reaction between the polymer (A) and the crosslinking agent (D), organic solvents that do not have functional groups that react with the polymer (A) and the crosslinking agent (D) components, such as esters such as ethyl acetate and butyl acetate, ketones such as methyl ethyl ketone and methyl isobutyl ketone, aromatics such as toluene and xylene, etc., can be used alone or in combination of two or more kinds.
[0155] <Urethanization catalyst (E)> The pressure-sensitive adhesive composition of the present invention preferably further contains a urethanization catalyst (E). As the urethanization catalyst (E), for example, an organometallic compound, a tertiary amine compound, etc. can be used. These can be used alone or in combination of two or more kinds.
[0156] Examples of the organometallic compound include zirconium-based compounds, iron-based compounds, tin-based compounds, titanium-based compounds, lead-based compounds, cobalt-based compounds, and zinc-based compounds. Examples of the zirconium compound include zirconium naphthenate and zirconium acetylacetonate. Examples of iron-based compounds include iron acetylacetonate and iron 2-ethylhexanoate. Examples of the tin compounds include dibutyltin dichloride, dibutyltin oxide, and dibutyltin dilaurate. Examples of titanium compounds include dibutyltitanium dichloride, tetrabutyltitanium, and butoxytitanium trichloride. Examples of lead-based compounds include lead oleate, lead 2-ethylhexanoate, lead benzoate, and lead naphthenate. Examples of the cobalt-based compounds include cobalt 2-ethylhexanoate and cobalt benzoate. Examples of zinc-based compounds include zinc naphthenate and zinc 2-ethylhexanoate.
[0157] Examples of the tertiary amine compound include triethylamine, triethylenediamine, and 1,8-diazabicyclo-(5,4,0)-undecene-7.
[0158] Of these urethanization catalysts (E), in terms of reaction rate and pot life of the pressure-sensitive adhesive layer, organometallic compounds are preferred, zirconium compounds are particularly preferred, and zirconium acetylacetonate is particularly preferred.
[0159] [Catalyst inhibitors] In the pressure-sensitive adhesive composition of the present invention, it is preferable to incorporate a catalytic action inhibitor into the urethanization catalyst (E) in order to extend the pot life and improve the coatability. Examples of the catalytic action inhibitor include β-ketoesters such as methyl acetoacetate, ethyl acetoacetate, octyl acetoacetate, oleyl acetoacetate, lauryl acetoacetate, and stearyl acetoacetate, and β-diketones such as acetylacetone, 2,4-hexanedione, and benzoylacetone. These are keto-enol tautomer compounds that protect the urethanization catalyst (E) and thereby reduce the catalytic activity of the urethanization catalyst (E) in a solution state, thereby suppressing an excessive increase in viscosity and gelation of the pressure-sensitive adhesive composition after blending, and thereby extending the pot life of the pressure-sensitive adhesive composition. Among these, it is preferable to use acetylacetone as the catalyst inhibitor from the viewpoint of the balance between pot life and curing speed. These catalyst inhibitors can be used alone or in combination of two or more.
[0160] The blending ratio (weight ratio) of the catalytic inhibitor to the urethanization catalyst (E) is preferably in the range of catalytic inhibitor:urethanization catalyst (E)=0.001:1 to 15:1, more preferably 0.005:1 to 13:1, and particularly preferably 0.01:1 to 10:1. If the content of the catalytic inhibitor is too low relative to the content of the urethanization catalyst (E), the pot life tends to be short and the coatability tends to be reduced, whereas if it is too high, the curing rate tends to be reduced.
[0161] In the pressure-sensitive adhesive composition of the present invention, in addition to the above-mentioned polymer (A), polyester resin (B), hydrolysis inhibitor (C), crosslinking agent (D), urethanization catalyst (E), etc., additives such as antioxidants such as hindered phenols, softeners, ultraviolet absorbers, silane coupling agents, stabilizers, antistatic agents, tackifiers other than the polyester resin (B), and other additives such as inorganic or organic fillers, powders such as metal powders, pigments, and particulate additives can be blended within the range that does not impair the effects of the present invention. These can be used alone or in combination of two or more kinds.
[0162] The tackifier other than the polyester resin (B) is not particularly limited, and conventionally known ones can be used, for example, terpene-based tackifiers, phenol-based tackifiers, rosin-based tackifiers, petroleum-based tackifiers, xylene-based tackifiers, epoxy-based tackifiers, polyamide-based tackifiers, ketone-based tackifiers, elastomer-based tackifiers, etc. are mentioned. Among them, it is preferable to use petroleum-based tackifier resins and terpene-based tackifiers, in terms of excellent tackiness and adhesive strength, and particularly styrene-based tackifiers and terpene-phenol-based tackifier resins are preferable. These can be used alone or in combination of two or more kinds.
[0163] When a tackifier other than the polyester resin (B) is blended, the amount is preferably 0.01 to 50 parts by weight, more preferably 0.1 to 30 parts by weight, even more preferably 1 to 20 parts by weight, and particularly preferably 3 to 10 parts by weight, relative to 100 parts by weight of the polymer (A), in terms of excellent tackiness.
[0164] In addition to the additives, the pressure-sensitive adhesive composition of the present invention may contain small amounts of impurities contained in the raw materials for producing the components of the pressure-sensitive adhesive composition.
[0165] Such a pressure-sensitive adhesive composition can be obtained, for example, by preparing the above-mentioned polymer (A), polyester-based resin (B) and necessary optional components, etc., and mixing and dispersing them during the production of polymer (A), or by mixing them into a solution of polymer (A) dissolved in an organic solvent and dispersing them using a mixing roller.
[0166] Moreover, the pressure-sensitive adhesive according to the present invention is made of the pressure-sensitive adhesive composition, that is, is obtained by crosslinking (curing) the pressure-sensitive adhesive composition.
[0167] The pressure-sensitive adhesive sheet of the present invention has a pressure-sensitive adhesive layer containing the pressure-sensitive adhesive. The pressure-sensitive adhesive sheet may be a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer on one or both sides of a supporting substrate, or may be a substrate-less double-sided pressure-sensitive adhesive sheet having no substrate. The pressure-sensitive adhesive sheet of the present invention is particularly suitable as a pressure-sensitive adhesive sheet for electronic components used for bonding electronic components. In the present invention, the term "sheet" includes "film" and "tape".
[0168] <Adhesive sheet> The pressure-sensitive adhesive sheet can be produced, for example, as follows. Such a pressure-sensitive adhesive sheet can be produced according to a known general pressure-sensitive adhesive sheet producing method. For example, the pressure-sensitive adhesive composition is applied to one side of a substrate, followed by drying to form a pressure-sensitive adhesive layer, and a release sheet is attached to the surface (the side opposite to the side in contact with the substrate) and cured as necessary to obtain the pressure-sensitive adhesive sheet of the present invention having a substrate and a pressure-sensitive adhesive layer, with the pressure-sensitive adhesive layer being provided on at least one side of the substrate.
[0169] Alternatively, the pressure-sensitive adhesive sheet of the present invention can be obtained by coating the pressure-sensitive adhesive composition on a release sheet, drying the composition to form a pressure-sensitive adhesive layer, laminating a substrate to its surface (the surface opposite to the surface in contact with the release sheet), and curing the layer as necessary.
[0170] In addition, a substrateless double-sided pressure-sensitive adhesive sheet of the substrateless type that does not have a substrate can be produced by forming a pressure-sensitive adhesive layer on a release sheet and laminating the release sheet to its surface (the surface opposite to the surface that contacts the release sheet) in addition to the above release sheet.
[0171] When using the resulting pressure-sensitive adhesive sheet or substrate-less double-sided pressure-sensitive adhesive sheet, the release sheet is peeled off from the pressure-sensitive adhesive layer, and the pressure-sensitive adhesive layer is attached to an adherend.
[0172] As the substrate, for example, a resin film, paper, cloth, a rubber sheet, a foam sheet, a metal foil, a composite of these, or the like can be used. Examples of the resin films include polyolefin films such as polyethylene (PE), polypropylene (PP), and ethylene-propylene copolymers; polyester films such as polyethylene terephthalate (PET); vinyl chloride resin films; vinyl acetate resin films; polyimide resin films; polyamide resin films; fluororesin films; polyurethane films; cellophane, and the like. Examples of the paper include Japanese paper, craft paper, glassine paper, fine paper, synthetic paper, and topcoat paper. Examples of the fabric include woven fabrics and nonwoven fabrics made of various fibrous materials, either alone or in admixture, etc. Examples of the fibrous materials include cotton, staple fiber, Manila hemp, pulp, rayon, acetate fiber, polyester fiber, polyvinyl alcohol fiber, polyamide fiber, polyolefin fiber, etc. Examples of the rubber sheet include a natural rubber sheet and a butyl rubber sheet. Examples of the foam sheet include a foamed polyurethane sheet, a foamed polyacrylic sheet, and a foamed polyolefin sheet. Examples of the metal foil include aluminum foil and copper foil. These substrates can be used as a single layer or as a multi-layer structure in which two or more types are laminated.
[0173] Among these, substrates made of polyethylene terephthalate, polyimide, foamed polyurethane sheet, foamed polyacrylic sheet, or foamed polyolefin sheet are particularly preferred, with polyethylene terephthalate being particularly preferred because of its excellent adhesion to the adhesive, and because it has excellent adhesive strength between the substrate and the adhesive, allowing the effects of the adhesive used in the present invention to be prominently exhibited.
[0174] As the release sheet, for example, various resin films exemplified above as the substrate, paper, cloth, rubber sheet, foam sheet, metal foil, composites thereof, etc. that have been subjected to a release treatment can be used. Among them, it is preferable to use a silicone-based release sheet as the release sheet.
[0175] When a resin film is used as the substrate, the thickness of the resin film substrate is not particularly limited. In order to avoid the pressure-sensitive adhesive sheet from becoming excessively thick, the thickness of the substrate film can be, for example, 200 μm or less, preferably 150 μm or less, more preferably 100 μm or less. In addition, depending on the purpose and mode of use of the pressure-sensitive adhesive sheet, the thickness of the substrate film may be 70 μm or less, 50 μm or less, 30 μm or less, 20 μm or less, or 10 μm or less. By reducing the thickness of the substrate film, the thickness of the pressure-sensitive adhesive layer can be made larger even if the total thickness of the pressure-sensitive adhesive sheet is the same. This can be advantageous from the viewpoint of improving adhesion to the substrate. The lower limit of the thickness of the substrate film is not particularly limited, but from the viewpoint of the handleability (handling ability) and processability of the pressure-sensitive adhesive sheet, it is usually 0.5 μm or more, preferably 2 μm or more, and particularly preferably 4 μm or more.
[0176] When a foam substrate is used as the substrate, the thickness of the foam substrate is not particularly limited and can be appropriately set according to the strength, flexibility, and purpose of use of the adhesive sheet. From the viewpoint of thinning the joint, the thickness of the foam substrate is usually 0.70 mm or less, more preferably 0.40 mm or less, particularly preferably 0.30 mm or less, and particularly preferably 0.2 mm or less. From the viewpoint of reducing the amount of chemicals penetrating into the adhesive interface, the thickness of the foam substrate is preferably 0.05 mm or more, more preferably 0.06 mm or more, particularly preferably 0.07 mm or more, and particularly preferably 0.10 mm or more. When the thickness of the foam substrate is large, impact resistance tends to be exhibited.
[0177] The pressure-sensitive adhesive composition may be applied using, for example, a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a bar coater, a knife coater, a spray coater, a comma coater, or the like.
[0178] As for the drying conditions after coating the pressure-sensitive adhesive composition, the drying temperature is preferably 60 to 140° C., and particularly preferably 80 to 120° C. The drying time is preferably 0.5 to 30 minutes, and particularly preferably 1 to 5 minutes.
[0179] The conditions for the above-mentioned aging treatment are generally room temperature (23°C) to 70°C, and generally 1 to 30 days. Specifically, the treatment may be performed under conditions such as 23°C for 1 to 20 days, preferably 23°C for 3 to 14 days, or 40°C for 1 to 10 days.
[0180] The thickness of the adhesive layer of the above-mentioned adhesive sheet and substrate-less double-sided adhesive sheet is not particularly limited, but is preferably 0.5 to 500 μm, particularly preferably 1 to 300 μm, further preferably 5 to 200 μm, and particularly preferably 10 to 100 μm. If the thickness of the adhesive layer is too thin, the adhesive strength tends to decrease, and if it is too thick, it becomes difficult to apply uniformly and problems such as air bubbles in the coating film tend to occur. In addition, when considering impact absorption, it is preferable to make the thickness 50 μm or more.
[0181] The thickness of the adhesive layer is determined by subtracting the measured thickness of the components other than the adhesive layer from the measured thickness of the entire adhesive sheet using a digital indicator (ID-C112B, manufactured by Mitutoyo Corporation).
[0182] The gel fraction of the pressure-sensitive adhesive layer is preferably 5% by weight or more from the viewpoint of chemical resistance and adhesive strength, particularly preferably 10 to 80% by weight, further preferably 15 to 60% by weight, and particularly preferably 20 to 40% by weight. If the gel fraction is too low, the cohesive strength decreases, and durability tends to decrease. However, if the gel fraction is too high, there is a concern that the adhesive strength will decrease due to an increase in the cohesive strength.
[0183] The gel fraction is an indication of the degree of crosslinking, and is calculated, for example, by the following method. That is, an adhesive sheet (without a separator) in which an adhesive layer is formed on a polymer sheet (e.g., a PET film, etc.) serving as a substrate is wrapped in a 200-mesh SUS wire netting, and immersed in toluene at 23°C for 24 hours, and the weight percentage of the insoluble adhesive component remaining in the wire netting after immersion relative to the weight of the adhesive component before immersion is taken as the gel fraction. However, the weight of the substrate is subtracted.
[0184] Furthermore, such a pressure-sensitive adhesive sheet may be provided with a release sheet on the outer side of the pressure-sensitive adhesive layer, if necessary, to protect the pressure-sensitive adhesive layer. In a pressure-sensitive adhesive sheet in which the pressure-sensitive adhesive layer is formed on one side of a substrate, a release treatment may be applied to the side of the substrate opposite to the pressure-sensitive adhesive layer, so that the release-treated surface can be used to protect the pressure-sensitive adhesive layer.
[0185] The pressure-sensitive adhesive of the present invention can be used for bonding various members, and is preferably used as a pressure-sensitive adhesive for optical members for bonding optical members. The pressure-sensitive adhesive layer of the pressure-sensitive adhesive composition can be laminated on an optical member to obtain the above-mentioned optical member with the pressure-sensitive adhesive layer.
[0186] It is preferable that the optical member with the pressure-sensitive adhesive layer further has a release film on the surface of the pressure-sensitive adhesive layer opposite to the optical member surface, and when the optical member is put into practical use, the release film is peeled off and the pressure-sensitive adhesive layer is attached to an adherend. As the release film, it is preferable to use a silicone-based release film. EXAMPLES
[0187] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "parts" and "%" are by weight unless otherwise specified. In the following examples, the glass transition temperature, weight average molecular weight, number average molecular weight, acid value, hydroxyl value, etc. were measured according to the methods described above.
[0188] The components were prepared as follows: The mol % of each component, which is a polybasic carboxylic acid, described in the following production examples of polyester resins indicates a molar ratio when the total amount of the polybasic carboxylic acids is taken as 100 mol %. Furthermore, the mol % of each polyol component described in the following Production Examples indicates the molar ratio when the total amount of polyol is taken as 100 mol %.
[0189] [Polymer A] [Production of polyester resin (A-1)] A reaction vessel equipped with a heater, a thermometer, a stirrer, a rectification column, a nitrogen inlet tube, and a vacuum device was charged with 386 parts of isophthalic acid and 146 parts of adipic acid as polyvalent carboxylic acids (a1), 113 parts of ethylene glycol, 216 parts of 1,6-hexanediol, and 138 parts of neopentyl glycol as polyols (a2), and 0.04 parts of germanium dioxide as a catalyst, and the internal temperature was gradually raised to 250° C., and an esterification reaction was carried out over 4 hours. Thereafter, the internal temperature was raised to 270° C., the pressure was reduced to 1.33 hPa, and a polycondensation reaction was carried out over 3 hours to obtain a polyester resin (A-1). The resulting polyester resin (A-1) had a glass transition temperature (Tg) of -5°C, a number average molecular weight of 10000, and a weight average molecular weight (Mw) of 33000. Other physical properties were as shown in Table 1 below. The final component ratio was isophthalic acid / adipic acid=70 mol % / 30 mol % as polyvalent carboxylic acids (a1), and ethylene glycol / 1,6-hexanediol / neopentyl glycol=35 mol % / 39 mol % / 26 mol % as polyols (a2).
[0190] [Polyester Resins (B-1) to (B-4)] [Production of Polyester Resins (B'-1) to (B'-4) before Endcapping] A reaction vessel equipped with a heater, a thermometer, a stirrer, a rectification column, a nitrogen inlet tube, and a vacuum device was charged with polyvalent carboxylic acids (a1) and polyol (a2) as shown in Table 2 below, and 0.04 parts of germanium dioxide as a catalyst. The internal temperature was gradually raised to 250°C, and an esterification reaction was carried out over 4 hours. Thereafter, the internal temperature was raised to 260° C., the pressure was reduced to 100 hPa, and the esterification reaction was carried out over one hour to obtain polyester resins (B'-1) to (B'-4) before endblocking. The resulting polyester resin (B'-1) before end-blocking had a final component ratio of isophthalic acid / adipic acid = 5 mol% / 95 mol% as polyvalent carboxylic acids (a1) and 1,6-hexanediol / neopentyl glycol = 40 mol% / 60 mol% as polyols (a2). The acid value was 0.1 mg KOH / g and the hydroxyl value was 92.2 mg KOH / g. The resulting polyester resin (B'-2) before end-blocking had a composition ratio of 100 mol% adipic acid as polyvalent carboxylic acid (a1) and 100 mol% 3-methyl-1,5-pentanediol as polyol (a2), and had an acid value of 0.1 mg KOH / g and a hydroxyl value of 227.5 mg KOH / g. The resulting polyester resin (B'-3) before end-blocking had a composition ratio of 100 mol% adipic acid as polyvalent carboxylic acid (a1) and 100 mol% 3-methyl-1,5-pentanediol as polyol (a2). The acid value was 0.2 mg KOH / g and the hydroxyl value was 115.3 mg KOH / g. The resulting polyester resin (B'-4) before end-blocking had a final component ratio of isophthalic acid / adipic acid = 50 / 50 mol% as polyvalent carboxylic acids (a1) and 3-methyl-1,5-pentanediol = 100 mol% as polyol (a2). The acid value was 0.1 mg KOH / g and the hydroxyl value was 56.0 mg KOH / g. The physical properties of the resulting polyester resins (B'-1) to (B'-4) before end-capping are shown in Table 2 below.
[0191] [Production of polyester resin (B-1)] Next, 40 parts of ethyl acetate and 19.6 parts of phenyl isocyanate as a blocking agent were added to 100 parts of the above polyester resin (B'-1) before end blocking, and the mixture was reacted at an internal temperature of 60°C for 4 hours to obtain a polyester resin (B-1) with blocked reactive molecular ends. The obtained polyester resin (B-1) had an acid value of 0.1 mgKOH / g and a hydroxyl value of 0.0 mgKOH / g. The obtained polyester resin (B-1) had no melting point, and no peak of heat of fusion (J / g) was observed.
[0192] [Production of polyester resin (B-2)] The polyester resin (B'-2) before the above-mentioned end blocking was treated in the same manner as the above-mentioned (B-1) except that 47.3 parts of phenyl isocyanate was used as the blocking agent, to obtain a polyester resin (B-2) with blocked reactive molecular ends. The obtained polyester resin (B-2) had an acid value of 0.1 mgKOH / g and a hydroxyl value of 4.6 mgKOH / g. The obtained polyester resin (B-2) had no melting point, and no peak of heat of fusion (J / g) was observed.
[0193] [Production of polyester resin (B-3)] The polyester resin (B'-3) before the above terminal blocking was treated in the same manner as (B-1) above, except that 24.0 parts of phenyl isocyanate was used as the blocking agent, to obtain a polyester resin (B-3) with blocked reactive molecular ends. The obtained polyester resin (B-3) had an acid value of 0.2 mg KOH / g and a hydroxyl value of 2.3 mg KOH / g. The obtained polyester resin (B-3) had no melting point, and no peak of heat of fusion (J / g) was observed.
[0194] [Production of polyester resin (B-4)] The polyester resin (B'-4) before the above terminal blocking was treated in the same manner as (B-1) above, except that 11.8 parts of phenyl isocyanate was used as the blocking agent, to obtain a polyester resin (B-4) with blocked reactive molecular ends. The obtained polyester resin (B-4) had an acid value of 0.1 mgKOH / g and a hydroxyl value of 0.6 mgKOH / g. The obtained polyester resin (B-4) had no melting point, and no peak of heat of fusion (J / g) was observed.
[0195] The physical properties of the polyester resins (B-1) to (B-4) with the reactive molecular ends blocked obtained above are shown in Table 3 below. In addition, dioctyl adipate, a fatty acid ester compound, was prepared as a comparison with the polyester resin (B). The physical properties of the fatty acid ester compound are also shown in Table 3 below.
[0196] [Hydrolysis inhibitor (C)] (C-1): Polycarbodiimide compound (manufactured by Nisshinbo Chemical Co., Ltd., "Carbodilite V-09GB")
[0197] [Crosslinking agent (D)] (D-1): Trimethylolpropane / tolylene diisocyanate adduct (manufactured by Tosoh Corporation, "Coronate L55E")
[0198] [Urethanization catalyst (E)] (E-1): Zirconium-based compound diluted with acetylacetone to a solids concentration of 1% (Matsumoto Fine Chemical Co., Ltd., "Orgatics ZC-150")
[0199] Example 1 The polyester resin (A-1) obtained above was diluted with ethyl acetate to a solid content concentration of 50%, and 30 parts of polyester resin (B-1), 0.5 parts of hydrolysis inhibitor (C-1), 4 parts (solid content) of crosslinking agent (D-1), and 0.05 parts (solid content) of urethanization catalyst (E-1) were blended with this polyester resin (A-1) (100 parts as solid content), and the mixture was stirred and mixed to obtain a pressure-sensitive adhesive composition.
[0200] Example 2 A pressure-sensitive adhesive composition was obtained in the same manner as in Example 1, except that the 30 parts of the polyester resin (B-1) was changed to 30 parts of (B-2) and the 4 parts of the crosslinking agent (D-1) was changed to 8 parts.
[0201] Example 3 A pressure-sensitive adhesive composition was obtained in the same manner as in Example 1, except that the 30 parts of the polyester resin (B-1) was changed to 50 parts of (B-3) and the 4 parts of the crosslinking agent (D-1) was changed to 7 parts.
[0202] Example 4 A pressure-sensitive adhesive composition was obtained in the same manner as in Example 1, except that the 30 parts of the polyester resin (B-1) was changed to 100 parts of (B-3) and the 4 parts of the crosslinking agent (D-1) was changed to 11 parts.
[0203] Example 5 A pressure-sensitive adhesive composition was obtained in the same manner as in Example 1, except that the 30 parts of the polyester resin (B-1) was changed to 50 parts of (B-4) and the 4 parts of the crosslinking agent (D-1) was changed to 5 parts.
[0204] Example 6 A pressure-sensitive adhesive composition was obtained in the same manner as in Example 1, except that the 30 parts of the polyester resin (B-1) was changed to 100 parts of (B-4) and the 4 parts of the crosslinking agent (D-1) was changed to 9 parts.
[0205] Example 7 A pressure-sensitive adhesive composition was obtained in the same manner as in Example 1, except that the 30 parts of the polyester resin (B-1) was changed to 150 parts of (B-4) and the 4 parts of the crosslinking agent (D-1) was changed to 11 parts.
[0206] Comparative Example 1 A pressure-sensitive adhesive composition was obtained in the same manner as in Example 1, except that the polyester resin (B-1) was not added and the crosslinking agent (D-1) was changed from 4 parts to 3 parts.
[0207] Comparative Example 2 An adhesive composition was obtained in the same manner as in Example 1, except that the polyester resin (B-1) was changed from 30 parts to 30 parts of (B'-4) and the crosslinking agent (D-1) was changed from 4 parts to 6 parts.
[0208] Comparative Example 3 An adhesive composition was obtained in the same manner as in Example 1, except that the 30 parts of polyester resin (B-1) was replaced with 30 parts of dioctyl adipate as the aliphatic acid ester compound, and the 4 parts of crosslinking agent (D-1) was replaced with 3.4 parts. Using the pressure-sensitive adhesive compositions obtained in the above Examples and Comparative Examples, pressure-sensitive adhesive sheets were produced as described below and evaluated as described below.
[0209] <Preparation of adhesive sheet with one-sided release film> The adhesive compositions obtained in Examples 1 to 7 and Comparative Examples 1 to 3 were applied onto a 38 μm-thick PET film (Toray Industries, Inc., "Lumirror T60") using an applicator and dried at 100°C for 3 minutes to obtain adhesive sheets with a PET film having an adhesive composition layer thickness of 25 μm. Next, the surface of the adhesive composition layer of the obtained adhesive sheet with PET film was covered with a 38 μm thick PET release film (Mitsui Chemicals Tocello, SP-PET-01-BU) and subjected to aging treatment at 40°C for 4 days to obtain an adhesive sheet with a one-sided release film.
[0210] [Gel fraction] The adhesive sheet obtained above was wrapped in a 200 mesh SUS wire net and immersed in toluene at 23°C for 24 hours, the weight of the adhesive component before immersion and the weight of the undissolved adhesive component remaining in the wire net after immersion were measured, and the percentage was calculated according to the following formula to obtain the gel fraction (%), except that the weight of the substrate was subtracted. Weight of undissolved adhesive component remaining in the wire net after immersion / Weight of adhesive component before immersion x 100 (%)
[0211] (Adhesive sheet evaluation) [Adhesive strength (initial)] The pressure-sensitive adhesive sheet with one-sided release film obtained above was cut to a size of 25 mm x 200 mm under an environment of 23°C and 50% RH, the release film was peeled off, and the pressure-sensitive adhesive layer side was pressed and attached to a mirror-finished stainless steel plate (SUS-BA plate) by reciprocating a 2 kg roller, and after leaving it to stand for 24 hours under the same atmosphere, the 180° peel degree (N / 25 mm) was measured using an autograph (Shimadzu Corporation, "Autograph AG-X 50N") at a peel speed of 300 mm / min. The evaluation criteria are as follows. (Evaluation Criteria) ○: More than 5N / 25mm, and the peeling state is at the adherend interface. △: More than 3N / 25mm and 5N / 25mm or less. The peeling state is at the interface of the adherend. × 3N / 25mm or less, or peeling state is cohesive peeling, substrate interface peeling, zipping peeling, adherend contamination
[0212] [Adhesive strength (after chemical resistance test)] The pressure-sensitive adhesive sheet with one-sided release film obtained above was cut to a size of 25 mm x 200 mm under an environment of 23 ° C. and 50% RH, and then the release film was peeled off, and the pressure-sensitive adhesive layer side was pressed and attached to a mirror-finished stainless steel plate (SUS-BA plate) by reciprocating a 2 kg roller, and aged for 30 minutes under the same atmosphere to obtain a measurement sample. Next, the measurement sample was immersed in a container containing isopropyl alcohol and left to stand for 24 hours under an atmosphere of 60 ° C. Thereafter, the measurement sample was taken out of the isopropyl alcohol, the attached isopropyl alcohol was blown off, and the sample was aged for 30 minutes under an environment of 23 ° C. and 50% RH, and the 180-degree peeling degree (N / 25 mm) was measured at a peeling speed of 300 mm / min using an autograph (manufactured by Shimadzu Corporation, "Autograph AG-X 50N"). The evaluation criteria are as follows. (Evaluation Criteria) ○: More than 5N / 25mm, and the peeling state is at the adherend interface. △: More than 3N / 25mm and 5N / 25mm or less. The peeling state is at the interface of the adherend. × 3N / 25mm or less, or peeling state is cohesive peeling, substrate interface peeling, zipping peeling, adherend contamination
[0213] [Holding force] The pressure sensitive adhesive sheet with one-sided release film obtained above was cut to a size of 25mm x 50mm in an environment of 23°C and 50% RH, the release film was then peeled off, and the sheet was pressed and attached to a stainless steel plate (SUS304) by reciprocating a 2kg roller (attached area 25mm x 25mm), and the holding power was measured for 24 hours at 60°C under a load of 1kg using a creep tester (Tester Sangyo Co., Ltd., holding power tester BE-501 with high temperature and humidity chamber). The evaluation criteria are as follows. (Evaluation Criteria) 〇 No misalignment △ Misalignment is 1.0 mm or less × Misalignment is greater than 1.0 mm or the item has fallen
[0214] [Tackiness] The pressure-sensitive adhesive sheet with one-sided release film obtained above was cut to a size of 12 mm x 12 mm under an environment of 23°C and 50% RH, the release film was peeled off, and a probe tack (TE-6001, manufactured by Tester Sangyo Co., Ltd.) was used to measure the following: probe diameter 5 mmΦ, push-in speed 10 mm / sec, pull-up speed 10 mm / sec, pressure time 5 seconds, and application pressure 1000 gf / cm 2 The probe tack was measured according to the following criteria: (Evaluation Criteria) ○ 0.8N or more ×...less than 0.8 N
[0215] [Table 1]
[0216] [Table 2]
[0217] [Table 3]
[0218] [Table 4]
[0219] The results in Table 4 above show that the pressure-sensitive adhesive sheets obtained from the pressure-sensitive adhesive compositions of Examples 1 to 7 are excellent in all of adhesive strength, chemical resistance, holding power, and tackiness. In contrast, the adhesive sheet obtained from the adhesive composition of Comparative Example 1 had chemical resistance and holding power, but zipping peeling was observed in the peeled state, and the tackiness was also poor. In Comparative Example 2, in which a polyester resin with unblocked reactive molecular ends was used, the peeled state and tackiness were also poor. Furthermore, in Comparative Example 3, in which a fatty acid ester compound was used instead of a polyester resin with blocked reactive molecular ends, the number average molecular weight of the fatty acid ester compound was small and there was no repetition due to ester bonds, so the compatibility with the polymer (A) was low, bleeding occurred, and the adhesive strength, chemical resistance, and tackiness were poor. This also shows that the adhesive composition containing the polyester resin with blocked reactive molecular ends has excellent adhesive properties. [Industrial Applicability]
[0220] The pressure-sensitive adhesive composition of the present invention is excellent in adhesive strength, holding power and tackiness, and therefore pressure-sensitive adhesives and pressure-sensitive adhesive sheets using the same can be suitably used for bonding electronic components, optical components, building components, and the like.
Claims
1. The composition comprises a polymer (A) and a polyester-based resin (B) having a structural unit derived from a polyvalent carboxylic acid (b1) and a structural unit derived from a polyol (b2), and having at least one reactive molecular end blocked, the polymer (A) is a polyester resin having a structural unit derived from a polyvalent carboxylic acid (a1) and a structural unit derived from a polyol (a2); A pressure-sensitive adhesive composition, characterized in that the content of the polymer (A) is 30% by weight or more based on the entire pressure-sensitive adhesive composition.
2. The pressure-sensitive adhesive composition according to claim 1, characterized in that at least one reactive molecular end of the polyester resin (B) is blocked with a blocking agent (b3) having a number average molecular weight of 50 to 5,000.
3. The adhesive composition according to claim 2, characterized in that at least one of the structural units derived from the polyvalent carboxylic acids (b1), the structural units derived from the polyol (b2) and the blocking agent (b3) contains an aromatic structural unit.
4. The pressure-sensitive adhesive composition according to any one of claims 1 to 3, characterized in that the polyester resin (B) has a glass transition temperature (TgB) of -80 to 30°C.
5. The pressure-sensitive adhesive composition according to any one of claims 1 to 4, characterized in that the polyester resin (B) has a number average molecular weight of 300 to 30,000.
6. The pressure-sensitive adhesive composition according to any one of claims 1 to 5, wherein the polyester resin (B) has a hydroxyl value of 10 mgKOH / g or less.
7. The pressure-sensitive adhesive composition according to any one of claims 1 to 6, characterized in that the acid value of the polyester resin (B) is 3 mgKOH / g or less.
8. The pressure-sensitive adhesive composition according to any one of claims 1 to 7, wherein the polyester resin (B) has a heat of crystalline fusion of 10 J / g or less.
9. 9. The pressure-sensitive adhesive composition according to claim 1, wherein the content of the polyester resin (B) is 0.1 to 180 parts by weight based on 100 parts by weight of the polymer (A).
10. The pressure-sensitive adhesive composition according to any one of claims 1 to 9, characterized in that the polymer (A) is a polyester-based resin containing an aromatic structural unit in at least one of a structural unit derived from a polyvalent carboxylic acid (a1) and a structural unit derived from a polyol (a2).
11. The pressure-sensitive adhesive composition according to any one of claims 1 to 10, characterized in that the polymer (A) has a glass transition temperature (TgA) of -70 to 40°C.
12. The pressure-sensitive adhesive composition according to any one of claims 1 to 11, characterized in that the glass transition temperature (TgA) of the polymer (A) is higher than the glass transition temperature (TgB) of the polyester resin (B).
13. A pressure-sensitive adhesive obtained by crosslinking the pressure-sensitive adhesive composition according to any one of claims 1 to 12.
14. A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer containing the pressure-sensitive adhesive according to claim 13.
15. The pressure-sensitive adhesive sheet according to claim 14, which is used for bonding electronic components.
Citation Information
Patent Citations
Tackifier resin for polyester-based adhesive and polyester-based adhesive composition
JP1998298528A
Polyester tackifier and adhesive composition
JP2003523444A
Adhesive layer, adhesive tape, and double-sided adhesive tape
JP2014169419A
Double-faced adhesive tape
JP2014196471A
Polyester plasticizer having a benzoic acid end cap
JP2017509729A